Multi-target antifungal mechanism of cinnamon essential oil against Colletotrichum musae and its effectiveness in preserving harvested banana fruit - Hongpeng Yu; Zizhen Li; Dong He; Kegang Wu; Xianghua Chai; Xuejuan Duan; Qiang An; Shengjian Wei (Postharvest Biology and Technology, 2027)

Exogenous phytohormone-assisted rotating algal biofilm reactor for enhanced polyacrylamide wastewater treatment and bioresource recovery - Huichao Zhang; Wuzhou Luo; Tianhao Wu; Zhongyi An; Jingwen Xu; Wenyunxi Shan; Dan Li (Bioresource Technology, 2026)

Effects of two enzyme–microbe co-fermented feed formulations on growth performance, ruminal fermentation, serum metabolome, and gastrointestinal microbiota in mid-fattening simmental heifers - Keren Yang; Ting Liu; Hanfang Zeng; Zhenling Wu; Xuanwei Lv; Daiwei Li; Zhiwen Xu; Liming Wei; Dehai An; Shicheng Wang; Chen Zheng (Animal Feed Science and Technology, 2026)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

DAU-Net: A density-adaptive unified attention network for long-tail fish counting in aquaculture - Zhengmeng Wu; Tongtong Gu; Chenyu An; Dashe Li; Shue Liu (Computers and Electronics in Agriculture, 2026)

Secondary forest succession shifts soil carbon priming from microbial to mineral control through dynamic microbe–mineral coupling - Panpan Wu; Jing Zhang; Xi'an Cai; Zhijian Mou; Yue Li; Wenjia Wu; Tengteng Li; Rong Mao; Zhanfeng Liu (Soil Biology and Biochemistry, 2026)

Intensifying floods may not imply cascading flood risks in dryland rivers - Xintong Gong; Qiang Zhang; Gang Wang; Xinning Gao; Linghua Qiu; Hushuang Ma; Anlan Feng; Zhi Li; Yungang Bai; Yaning Chen; Xuelian An; Xiaoqing Wu (Journal of Hydrology, 2026)

Microwave-assisted sulfonation of spent polypropylene separator for conversion into high-performance carbon anode for sodium-ion batteries - Chao Li; Yinyi Gao; Yang An; Kai Zhu; Pengwei Li; Hongbin Wu; Hao Sun; Dianxue Cao (Journal of Environmental Chemical Engineering, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

Ambient-air fabrication of high-performance thick-film organic solar cells enabled by solid additive engineering - Kun Li; Cunbin An; Yuan Yao; Jianbin Zhong; Bin Hu; Wei Zhang; Yishi Wu; Bowei Xu; Dianyi Liu; Guanghao Lu; Qing Liao; Xiaozhang Zhu; et al. (Chemical Engineering Journal, 2026)

A honeycomb film containing self-assembling microgels for long-term live microbiota preservation - Yudi Shen; Fupei Xu; Tingtao An; Yueru Li; Jingmin Liu; Jing Wu; Shuo Wang (Chemical Engineering Journal, 2026)

Elevation-dependent variations in snow cover and their response to climate and the polar vortex in the Altai mountains - Jiarui Li; Wei Zhang; Xuejiao Wu; An'an Chen; Xinyue Zhong; Yongping Shen (Atmospheric Research, 2026)

UEV1A attenuates MDA5-mediated antiviral immune response by reducing its ubiquitination and aggregation - Jiaxin Wang; Rongyao Sun; Ting Li; Houcheng Liang; Huan He; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2026)

Bio-instructive polyetheretherketone implants combat implant-associated bone infections through inducing bacterial cuproptosis-like death and promoting peri-implant immune remodeling - Weinan Yang; Tao Zhang; Yongwei Zhou; Zizhan Su; Zihao An; Congsun Li; Jiaxuan Zou; Wushi Cui; Wentao Chen; Jian Xiao; Tao Sun; Shicheng Wang; et al. (Chemical Engineering Journal, 2026)

pH-switchable polyoxometalate-loaded hydrogel with intrinsic oxygen-independent singlet oxygen generation and in situ nitric oxide production for infected wound management - Cantong Sun; Zhen Zhang; Zhen Li; Muhammad Adnan Younis; Hongyu Chen; Shujun Zhang; Junle Wu; Dehao Du; Haiyan Ge; Lehao Liu; Ruiheng Li; Shengyi Dongye; et al. (Chemical Engineering Journal, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Marine productivity responses to the deglaciation following the late Paleozoic Ice Age in the Tethyan Lhasa Block - Keying Wu; Xianyin An; Yong Du; Wenfeng Zhou; Qiang Fang; Xiaolong Liu; Yifan Xiao; Li Tian (Chemical Geology, 2026)

New enantiomers from Ficus variolosa Lindl. ex Benth. and their anti-inflammatory and neuroprotective activities - Ling-Fei Tong; Yu-Qiong Lu; Qing Li; Shun Pan; Hui Li; An Jin; Wen-Ming Wu (Natural Product Research, 2026)

Protective Effects of Double-layered Multinucleated Microcapsules Containing Bifidobacterium adolescentis FS2-3 Against Enteritis Mediated by Different Pathogens - Jiayi Tang; Henan Zhang; Danli Yan; Tong Li; Zijing Li; Yulian Zhao; Ying Wang; Feiyu An; Jia Guo; Kexin Zheng; Natalia Alekseevna Golovneva; Junrui Wu; et al. (Probiotics and Antimicrobial Proteins, 2026)

Mechanisms of extreme rainfall partitioning in contour ridge system: A modified SCS-CN method incorporating microtopographic and ridge geometry effects - Juan An; Guohui Li; Ruofei Liu; Yuanzhi Wu; Xiyuan Wu; Rui Zhang; Yao Zhao (Soil and Tillage Research, 2026)

Retraction notice to “Treatment to surfactant containing wastewater with membrane distillation membrane with novel sandwich structure” [Sci. Total Environ. 867 (2023) 161195] - Hanyu Guo; Haifu Gao; An Yan; Xiaolong Lu; Chunrui Wu; Li Gao; Jianhua Zhang (Science of The Total Environment, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Toddacoumalins A-J, ten undescribed coumarins from the roots of Toddalia asiatica - Feng Wu; Han Yao; Xin-Rui Liao; Nan An; Xing-Shu Li; Wen-Hao Hu; Albert S.C. Chan; Hou-Jin Li; Wen-Jian Lan (Phytochemistry, 2026)

A triplex-readout CRISPR-Cas12a multimodal biosensing platform for point-of-care detection of avian influenza H5N1 - Bin Guo; Yang Li; Mengxin Shi; Jingyu Zhang; Qingqing Wu; Xiaokang Wu; Ruifang An; Fu Wang (Journal of Hazardous Materials, 2026)

Magnetotactic bacteria antagonized lead toxicity: Distinct detoxification mechanisms in magnetosome-containing/deficient bacteria - Ruoyun Dong; Yuting Ding; Han Li; Yanan Zhao; Yuanyuan Wu; Chenxi Zhou; An Xu; Yun Liu (Journal of Environmental Sciences, 2026)

Abscisic acid promotes sweet cherry fruit cracking dependent on cell wall disassembly - Ruie Liu; Li Wang; Zixing Sun; Zhuo Yan; Xiaojuan An; Wanxia Sun; Honglin Nong; Muhammad Usman; Zuoyan Qin; Songtao Jiu; Long Chen; Yaqin Wu; et al. (Food Research International, 2026)

Eccentric coaxial wet-spun magnetic composite actuators with decoupled magneto-pneumatic shape-morphing for biomedical applications - Ping-an Yang; Yixuan Han; Chunyan Mo; Mengjie Shou; Rui Li; Yi Lu; Decheng Wu; Qiao Chen; Zhiwei Huang (Chemical Engineering Journal, 2026)

A hierarchical thermal preference structure for understanding satisfaction in multi-occupant offices under cooling season conditions - Jingjing An; Qixuan Li; MingYang Qian; Da Yan; Ruosa Wu; Xin Zhou (Building and Environment, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

CARE Radiative Transfer Model: A Tool for Supporting Polarization and Hyperspectral Radiative Transfer Simulation in the Coupled Atmosphere–Ocean System - Chong Shi; Husi Letu; Teruyuki Nakajima; Miho Sekiguchi; Wenwu Wang; Ruijie Yao; Huazhe Shang; Shuai Yin; Jian Xu; Ni An; Wenke Jiang; Yuxiang Cui; et al. (Advances in Atmospheric Sciences, 2026)

Occurrence and potential sources of greenhouse gases at Wuzhen, a typical ancient water town in Eastern China - Zheng Xia; Jiasi Shen; Peipei Shao; Wenlong Zhao; Bingye Xu; Xudong Tian; Yang Wu; Changlin Zhan; Saiya An; Nan Li; Zhengning Xu; Bo Yao; et al. (Environmental Monitoring and Assessment, 2026)

Nitrogen limitation enhances Irgarol 1051 toxicity by aggravating PSII photoinhibition in the marine diatom Thalassiosira weissflogii - Yuheng An; Shumin Zeng; Futian Li; Jun Wang; Xuexia Zhu; Juntian Xu; Yaping Wu (Marine Environmental Research, 2026)

Stable cerium isotope fractionation during basalt-rhyolite magmatic differentiation - Peng Wu; Fang Liu; Lei Li; Zhengjie Zhao; Jiaojiao Wu; Wenke Wang; Yajun An; Xin Li; Paul Savage; Mingxing Ling; Zhaofeng Zhang (Geochimica et Cosmochimica Acta, 2026)

BaP and 17β-estradiol affect retromer-VPS35, restricting pro-survival transcription and exacerbating neurotoxicity in a reclaimed water environment - Liang Xu; Chuanbing Wu; Yu Xia; Mengyuan An; Peng Wang; Wansheng Zhang; Wenwen Li; Yuhan Zhou; Junkai Hao; Dazhi Sun; Zhipeng Zhang; Caiyun Sun (Aquatic Toxicology, 2026)

Experiments of orthometric height determination by transportable clock referred to GNSS time - Lei Wang; Lihong Li; Pengfei Zhang; Wei Xu; An Ning; Rui Xu; Ziyu Shen; Kuangchao Wu; Wenbin Shen (Advances in Space Research, 2026)

Associations of Fluke (Spirorchiid) Infection and Buoyancy Disorder with Death in Stranded Sea Turtles Undergoing Rehabilitation in Taiwan - Ming-An Tsai; I-Chun Chen; Pei-Qi Ye; Po-Yu Wu; Tsung-Hsien Li (Journal of Marine Science and Engineering, 2026)
Sea turtles are increasingly regarded as indicators of coastal ecosystem health, as their clinical condition and disease profiles reflect prolonged exposure to environmental pressures in impacted marine habitats. Wildlife rehabilitation facilities play an important role in sea turtle conservation, although risk factors associated with mortality during rehabilitation are not well defined. This retrospective study evaluated clinical and infectious risk factors for death in 108 stranded sea turtles (including 70 green turtles, 19 olive ridley turtles, 16 hawksbill turtles, 2 loggerhead turtles, and 1 leatherback turtle) admitted to the rehabilitation facility at the National Museum of Marine Biology and Aquarium between 2018 and 2024. Data on buoyancy disorder, spirorchiid fluke infection, fibropapillomatosis and final disposition were analysed using univariate and multivariable logistic regression. Buoyancy disorder (adjusted OR = 9.96) and spirorchiid fluke infection (adjusted OR = 3.33) were associated with increased mortality, highlighting the need for careful monitoring and early detection of these conditions during rehabilitation. However, the retrospective design may inherently limit causal inference.

Development and experimental analysis of an annular slit pneumatic granular fertilizer flow rate detection device based on fertilizer flow convergence technique - Xinhe Shan; Bingxin Yan; Xiaofei An; Changhai Luo; Liwei Li; Yanxin Yin; Qingzhen Zhu; Zhijun Meng; Guangwei Wu (Computers and Electronics in Agriculture, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Macrophyte restoration alters sedimentary organic matter-microbes-environment interactions and enhances carbon sequestration in lake sediment - FengTing Wu; ShiLin An; JingJing Liu; YueHan Lu; Hu He; XiaoZi Chang; Qi Leng; ShengHao Zhang; Peng Xing; KuanYi Li; YingXun Du (Water Research, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Assessing humus to predict soil organic carbon in Northwest China: A case study of Ningxia - Xinnian GUO; Zhuonan HOU; Xia WU; Huaiyu LONG; Zehua XU; Baiyun LI; Shaoshan AN (Pedosphere, 2026)

Dual repression of OsSnRK1β1A by the deubiquitinase OsOTUB1 orchestrates energy metabolism and grain yield in rice - Ludan Zhang; Pengfei Wang; Yue Li; Shuang Yang; Yan Chen; Zhiying Ma; Jing Pan; Xiaoyu Wang; Chenyan Wang; Haoyuan An; Yuqing Xu; Yifei Xiao; et al. (Molecular Plant, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Exogenous phytohormone co-application enhances polyacrylamide removal and microalgal-bacterial biofilm development in a revolving algal biofilm reactor - Zhongyi An; Renrunbang Li; Tianhao Wu; Huichao Zhang; Jingwen Xu; Qingbin Zhao; Dongrun Sui; Dan Li (Journal of Environmental Chemical Engineering, 2026)

Engineering directed charge transport pathway in MOF@COF hetero-framework for enhanced singlet oxygen production and tetracycline photo-oxidation - Xiaorui Du; Lifei Liu; Pengfei Li; Luyuan Zhang; Yang Deng; Xia An; Xu Wu (Journal of Environmental Chemical Engineering, 2026)

Multi-omics approach reveals the molecular basis of ToMMV-induced resistance and its effects on tomato fruit quality - Yan Wang; Hongwei Chen; Kexin Cao; Yan Li; Kexin Liu; Dan Zhang; Dong Jiang; Xupeng Lu; Zihao Xia; Junbo Luan; Mengnan An; Yuanhua Wu (Food Chemistry, 2026)

Acidic substances generation patterns and regulation strategies in the Caosha and first rounds of Jiangxiangxing Baijiu fermentation - Ying Guo; Zhenyao Zhang; Jiajie Li; Songbo Guo; Pengpeng Sun; Kaiyuan An; Yumei Wang; Ruixin Wang; Ying Zhou; Xiaole Wu; Yefu Chen (Food Bioscience, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Chemical constituents from the roots of Rubus crataegifolius Bunge and their chemotaxonomic significance - Wei Liu; Yu-Li Zhang; Piao Yan; Ze Wu; Meng-Wei Gao; Shuo Tian; Ren-Bo An; Li-Li Jin (Biochemical Systematics and Ecology, 2026)

Plug-and-Play Frequency-aware Channel Modulation for Potato Price Forecasting - An Zhang; Guiyuan Li; Xiujian Wu (Potato Research, 2026)

Impact of land use transition on ecosystem services in the Yangtze River economic belt and associated mechanism - Youzhi An; Mengsha Fan; Zhihao Tao; Peng Zhao; Hualin Chen; Da Li; Yun Wu; Qiuju Wu; Jin Sun; Feng Xu; Fengtai Zhang (Environment, Development and Sustainability, 2026)

Microsphazaphilones H–Y: new azaphilone pigments with HIV latency reversal activity from the marine-derived fungus Microsphaeropsis arundinis P1B - Qing-Ren Lu; Xian-Yuan Yang; Lei Li; Lei-Ming Wu; Lu-Xiang Wan; Yi-Fan Fu; Xian-An Chen; Xin-Xiang Xu; Tao Yuan; Xin Chen; Abrar Ahmed; Nirmal Malik; et al. (Marine Life Science & Technology, 2026)

CYP303A1 contributes to thiamethoxam resistance in the small brown planthopper, Laodelphax striatellus (Fallén) - Futao Gao; Yubiao Cai; Zihao Wang; Junhua Zhu; Wenyan Li; Youwu Hao; Li Wang; Jiakai Wu; Yingdang Ren; Shiheng An; Xinming Yin; Xiangyang Liu (Crop Protection, 2026)

Integrated in-situ electrochemical-membrane process for ammonia valorization and sustainable water reuse - Paula Jungwon Choi; Xinning Zhang; Wing Chi Au; Adel Tayara; Noman Khalid Khanzada; Yingying Xiang; Li Ling; Di Wu; Am Jang; Ho Kyong Shon; Chii Shang; Guanghao Chen; et al. (Water Research, 2026)

Insights into microplastic migration through polymer-modified geosynthetic clay liners under dry-wet cycles - Shuai Liang; Cong Zhao; Guanping An; Zheng Wu; Lei Li; Chunxiao Meng; Daoping Peng (Waste Management, 2026)

Surface-water estradiol–benzo[a]pyrene mixtures: Transcriptomics in a PC12 neuronal differentiation model nominate an E2F1–PTPRO axis as a candidate mechanistic biomarker - Caiyun Sun; Peng Wang; Yu Xia; Mengyuan An; Shuang Liu; Chuanbing Wu; Wansheng Zhang; Wenwen Li; Yuhan Zhou; Junkai Hao; Liang Xu (Toxicology Letters, 2026)

Nano-bioprotectant dsRsGH1@ε-PL@CMCS enhances RNAi efficacy against Rhizoctonia solani via dual mechanisms: Interacting with the vesicle transport protein SEC22 and modulating the tobacco phyllosphere microbiota - Xiaojie Ding; Kexin Cao; Yan Li; Xinchun Li; Qiu Zhong; Yong Chen; Mengnan An; He Liu; Rujun Zhou; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Dibenzocyclooctadiene lignans from Kadsura coccinea and their immunosuppressive activities - An Jin; Zhuocan Huang; Hui Li; Jinling Chang; Hanli Ruan; Wenming Wu (Phytochemistry, 2026)

Geniposide ameliorates ferroptosis through the ROS/p38 MAPK/NCOA4/GPX4-mediated ferritinophagy in a co-culture system of HMC3 and SH-SY5Y cells - Liang-Jun Wang; Yu-Chin Chang; Li-Mei An; Bin-Nan Wu (NeuroToxicology, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Regionalized optimization of piggery wastewater treatment technologies in China: Life cycle assessment unlocking environmental benefits through hydrothermal carbonization and spatially tailored solutions - Beier Shang; Nan An; Bingyan Wu; Peiyu Tian; Jianshuo Shi; Qing Chen; Yangyang Li (Journal of Cleaner Production, 2026)

Re-evaluating the role of iron and manganese oxides in thallium retention: Insights from laboratory adsorption and soil pot experiments - Xian’an Yu; Yifan Guan; Jing Wei; Pengjie Hu; Jiawen Zhou; Tong Zhou; Zhu Li; Tangfu Xiao; Juan Liu; Yongming Luo; Peter Christie; Longhua Wu (Journal of Environmental Sciences, 2026)

High-sensitivity and ultra-wide-range flexible piezoresistive sensor with surface microsphere and gradient cell structure for human gait correction - Xiangfang Peng; Shengguo Gu; Wen Xiao; Yuhuan Lin; Shulei Wu; Shuai Wang; Bin Tan; Haoyang Mi; Suiyi Li; Zhixiang Cui; Yongchao Xu; Feifan Yi; et al. (Chemical Engineering Journal, 2026)

In-site fabrication of pheromone-loaded core-sheath fibers via handheld emulsion electrospinning with natural surfactants for Apolygus lucorum attraction - Hai-yan Ye; Wen-jie Shangguan; Han Wu; Jing Zhao; Liu-bin Xiao; De-jin Xu; Guang-chun Xu; Qi-liang Huang; Guo-hui Zhang; Li-dong Cao; Yong-an Tan (Chemical Engineering Journal, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Elucidating the synergistic SO2 tolerance mechanism in Cu-doped BiFeO3 electrocatalysts for sustainable nitrate reduction - Yuxiang Li; Yaao Li; Qian Yang; Ting An; Xiao Cui; Liuyun Lai; Yaoxin Wu; Chenxia Yang; Dalei Chang; Aiqun Kong; Denghao Wang; Jiajun Wang; et al. (Chemical Engineering Journal, 2026)

Accumulation effects, driving mechanisms, and primary tolerance strategies of trace metals in mangrove-sediments system - Qiong Tao; Weiheng Qin; Yipeng An; Jinli Huang; Chunxiang Liu; Jin Luo; Haitao Chen; Wenhui Liao; Bingxin Li; Zhangpeng Lu; Zhuokai Wu; Gang Luo; et al. (Plant and Soil, 2026)

Disentangling litter decomposition trajectories in streams: Ecological insights from a global multimodel analysis - Kai Yue; Matthias C. Rillig; Koenraad Van Meerbeek; Siying Chen; Qiqian Wu; Yan Peng; Kun Guo; Zimin Li; Xin Peng; Yuexin Fan; Nannan An; Xiangyin Ni; et al. (Ecology, 2026)
Stream litter decomposition is a key ecosystem function commonly modeled using a single exponential decay function. However, the flow‐driven nature of stream environments may lead to temporally heterogeneous decay dynamics that are poorly captured by this approach. Here, we evaluated the decomposition process of leaf litter in streams with four decomposition models (single exponential, double exponential, asymptotic, and Weibull) using 523 time series observations across the globe. Results showed that (1) the single exponential model provides a simple and reliable description of litter decomposition dynamics and captures a broad temporal pattern of mass loss; (2) double exponential and asymptotic models were applicable to only a subset of observations, whereas the Weibull model showed relatively consistent applicability across datasets; and (3) climate zone, leaf type, litterbag mesh size, and stream water temperature emerged as the key factors associated with decomposition parameters from different models. Overall, our results suggest that the single exponential model provides a robust description of stream litter decomposition, whereas alternative formulations such as the Weibull model could provide complementary views of decomposition dynamics in stream ecosystems.

Targeting angiopoietin-like protein 3 and interleukin-1β alleviated liver and kidney injury through attenuation of lipotoxicity and regulation of glycolipid metabolism in db/db mice - Shuwen Xu; Longfei Wang; Zihan Dou; Xiaozhi Hu; Zhonglian Cao; Yuanzhen Zhang; Xianhan Jiang; Tao Wu; Zhuojin Li; Yanyang Nan; An Zhu; Yu Bai; et al. (Inflammation Research, 2026)

Comparative assessment of reproductive and intergenerational toxicity of perfluorooctanoic acid and hexafluoropropylene oxide trimer acid in zebrafish (Danio rerio) - Shenggan Wu; Xuehua An; Ting Xu; Dou Wang; Zhenlan Xu; Yuanxiang Jin; Xinquan Wang; Yun Li; Yanhua Wang (Journal of Hazardous Materials, 2026)

Electrodeposition and electrocatalytic hydrogen evolution performance of Ni–Mo, Ni–W and Ni–Mo–W cathodes for alkaline water electrolysis: A comparative study - Yu-Ao An; Wangping Wu; Lingqi Kong; Yantao Jiao; Xin Li; Mohammed Mukhtar Yusif; Qinqin Wang (Fuel, 2026)

A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Multi-scale quantile neural network for air quality index prediction - Shangrui Zhao; Weiqi Yu; Xi’an Li; Jing Xu; Jinran Wu (Theoretical and Applied Climatology, 2026)
Accurate forecasting of the Air Quality Index (AQI) is essential for mitigating the adverse environmental and public health impacts associated with air pollution. However, existing predictive models often exhibit limited robustness to extreme outliers and struggle to effectively capture multi-scale temporal dependencies and associated uncertainties. To address these challenges, this study proposes a novel Multi-scale Quantile Neural Network (MQNN) framework that integrates Fourier expansion for temporal feature extraction and the pinball loss function for probabilistic quantile estimation. Specifically, the AQI time series is first decomposed via Fourier expansion to capture multi-scale temporal dynamics. These transformed features are then processed through multiple parallel subnetworks, each trained to predict a distinct quantile using the pinball loss. The overall training objective aggregates the loss across all time steps and quantiles, with optimization proceeding until convergence. The proposed MQNN model is empirically evaluated using AQI datasets from five major cities in China. Experimental results demonstrate that MQNN consistently outperforms conventional machine learning and deep learning baselines, achieving higher accuracy and more reliable uncertainty estimation. Furthermore, the MQNN framework facilitates the identification of dominant pollutants, offering actionable insights for targeted air quality management and policy interventions. While the MQNN model has strong predictive capabilities, its computational cost remains high for high-dimensional inputs. Moreover, integrating external information may further improve prediction accuracy and enhance the model’s applicability in real-world scenarios.

Frequency-Aware and Residual-Attention CGAN with Two-Stage Training for Imbalanced Potato Leaf Disease Detection in Crop Management - An Zhang; Chao Wu; Guiyuan Li; Sheng Chen (Potato Research, 2026)

Paleoproterozoic granite chronology, geochemical characterization, and geological significance in the Longdu region of northeastern Zambia - Yu-Xuan Wu; A-Lei Gu; Jun-Ping Ren; Ling-An Bai; Li-Bo Zuo; Hong-Wei Sun; Shi Xing; Zi-Jiang Liu (International Geology Review, 2026)

Flocoumafen exposure induces skeletal developmental toxicity and neurotoxicity in zebrafish (Danio rerio) - Tianyi Chen; Fengjun Fan; An Cheng; Yumei Xia; Haoze Chen; Jiakai Fang; Yangyu Chen; Tianjia Li; Anli Wang; Binjie Wang; Weixuan Yao; Yuanzhao Wu (Toxicology Letters, 2026)

Cultivar-dependent effects of arbuscular mycorrhizal (AM) fungal inoculation on fruit quality and native AM fungal community in navel orange - Xin-Ping Tan; Cheng-Zhuo Li; Ying-Ning Zou; An-Qi Lei; Mashael Daghash Alqahtani; Qiang-Sheng Wu (Rhizosphere, 2026)

MdCNGC15B, a cyclic nucleotide-gated channel (CNGC) protein, positively regulates the tolerance to drought and salt stress in apple - Xin-Long Guo; Hong-Liang Li; Xiang Wu; Tian-tian Wang; Yan-yan Guo; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2026)

Whole genome sequencing reveals transmission dynamics and persistence of Listeria monocytogenes along the poultry slaughtering and processing chain - Ye Wang; Chaohui Huang; Sijie Wu; Jianye Jia; Tianxiang Pan; Ruochen Wang; Jing Li; Zegang Wang; Chuang Meng; Yuelan Yin; Xin'an Jiao (International Journal of Food Microbiology, 2026)

In silico discovery of a novel sheep whey protein-derived antimicrobial peptide: antimicrobial activity, mechanism of action, and application - Shuaiqi Ji; Mengxue Lou; Feiyu An; Yilin Chou; Yi Zhu; Jiawei Guo; Meichao Luo; Taowei Zhang; Wenqian Li; Xinyi Zhang; Rina Wu; Junrui Wu (Food Bioscience, 2026)

Hydrothermal stress influences the spatial distribution pattern of soil organic carbon and its stock in Xinjiang - Yunhao Li; Mingjie Shi; Ping'an Jiang; Jinzhi Gu; Jia Guo; Jiahao Zhao; Gongxin Wang; Yanmin Fan; Hongqi Wu (CATENA, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Immune modulation of Spodoptera litura larvae parasitized by Meteorus pulchricornis and role of the host β-1, 3-glucan-binding protein in parasitism success - Yan Song; Zhi-Xiang Liu; Feng-ming Gu; Ping Li; Wei-Hong Zhou; Jun Wang; Fu-An Wu; Sheng Sheng (Pesticide Biochemistry and Physiology, 2026)

Mitochondrial Complex I hyperactivation drives PET microplastic-induced intestinal bioenergetic collapse - Chuxin Zhang; Wenjing Li; Jiaxing An; Guodong Cao; Yitao Yan; Hao Chen; Huimei Yu; Chao Zhang; Juan Shao; Haitao Zhou; Zhifang Wu; Sijin Li; et al. (Journal of Hazardous Materials, 2026)

Bioactive nanoreactor-enhanced injectable polysaccharide hydrogels for tissue regeneration and scar suppression via multifactorial regulation in infected burn wounds - Junyao Li; Xiaochen Wu; Xintao Gao; Jingtong An; Qishan Xu; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Plant growth-promoting functions of endophytic Fusarium annulatum alleviate the damage caused by saline stress in rice - Haoyu Cai; Tongtong Liu; Jiafeng Yu; Wenchao Sun; Lingyun Chang; Shengyi Liu; Ziguang Liu; Junze An; Weilin Cui; Yumei Li; Juan Wu (Planta, 2026)

Role of Microglial Dysfunction in Parkinson’s Disease: From Multifactorial Causes to Neurodegeneration - Yuxiang Xu; Tingting Han; Yue Wu; Haixuan Liu; Keyuan Hou; Zhaowu An; Yongjie Li; Chaoyang Zhu; Song Wang; Jianshe Wei (Neuroscience Bulletin, 2026)

A traceability investigation of the 2023 Xinjing open-pit coal mine landslide: remote sensing analysis using spaceborne SAR and optical imagery - Hong’an Wu; Yonghong Zhang; Xiaoxue Sun; Ying Liu; Zhong Lu; Yonghui Kang; Jujie Wei; Kui Yang; Baipeng Li; Nan Liu; Liqiang Deng (Landslides, 2026)

A novel duplication mutation in the MYO7A gene associated with autosomal recessive hearing loss in a Chinese family - Jie Li; Shengmei Yang; Mina Xiang; Qingling An; Yuannan Wu; Qingli Quan; Haiou Jiang (Genes & Genomics, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Scale-up synthesis and antiviral mechanisms of novel fluorine-containing cytidine peptide compound SN15: Insights from transcriptomic and proteomic analyses - Miao Yu; Chuantao Xu; Yan Wang; Shidong Zhou; Jingwen Li; Zihao Xia; Mengnan An; He Liu; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Vibration suppression in floating offshore wind turbines after blade pitch control system failure using tuned mass damper - Yong Yue; Xin Jin; Fei Li; Mengjie Luo; An Wu; Chinglin Kuo (Ocean Engineering, 2026)

Carbonic anhydrase modulates photosynthetic responses to UV radiation in diatoms across temperature gradients - Xiangyu Li; Yuheng An; Juntian Xu; Yaping Wu; John Beardall (Journal of Photochemistry and Photobiology B: Biology, 2026)

Machine learning-driven screening of characteristic flavor compounds: Investigating the impact of ultra-high pressure treatment on the flavor of Tibetan chicken soup - Kai Dong; Xinyuan Huang; Yingmei Wu; Guofeng Jin; Yufang Guan; Hongbo Song; Fengping An; Xin Li; Erhao Zhang; Qun Huang (Food Research International, 2026)

RrLHY regulates arginine biosynthesis by activating RrNAGS1 in Rosa roxburghii fruit - Xufeng Yang; Nanyu Li; Richard Ludlow; Qianmin Huang; Zhaoxin Wu; Liangliang Li; Hong Nan; Huaming An; Min Lu (Plant Cell Reports, 2026)

Fatty Acid-binding Protein 4 Exacerbates Blood–brain Barrier Disruption Through the JNK/c-Jun/MMP12 Pathway After Traumatic Brain Injury - Botao Ma; Dezhen Yang; Mengwu Tian; Shimei Dai; Zhuang Jing; Xuerui He; Xiaoqing Bao; Yinbo Long; Yu Gong; Yanling Dong; Jiaming Li; Gengshen Zhang; et al. (Molecular Neurobiology, 2026)

Measuring intercontinental-scale geopotential difference using atomic clock frequency comparison with PPP technique - Kuangchao Wu; Wen-Bin Shen; Hok Sum Fok; Zengzeng Lian; Pengfei Zhang; Lihong Li; Lei Wang; An Ning; Rui Xu; Ziyu Shen (Advances in Space Research, 2026)

Biocontrol efficiency and potential mechanism of dimethyl trisulfide against postharvest Diplodia stem-end rot in pummelo (Citrus maxima) - Yankun Lin; Shun Feng; Haijin Cai; Haibo Wang; Xiuli Zhang; Fangfang Wu; Shuoyu An; Xinguo Li (Postharvest Biology and Technology, 2025)

Numerical investigation into the unsteady flow characteristics around a fully appended SUBOFF model combined with a pump-jet propulsor - Shuting Cai; Renfang Huang; Ning Li; Yi An; Qiang Wu; Yiwei Wang (Ocean Engineering, 2025)

Numerical insights into thermal-hydraulic-mechanical-damage (THMD) fields evolution over hydraulic fracturing in hot dry rock - Xiaotian Wu; Yingchun Li; Tianjiao Li; Guanglei Cui; Chun'an Tang (International Journal of Rock Mechanics and Mining Sciences, 2025)

Multi-omics analysis reveals PkNF-YA7a as a transcriptional activator that promotes glycerolipid biosynthesis in Pinus koraiensis seeds - Zeyu An; Yuxin Song; He Zhang; Xin Wang; Dongran Zheng; Peitian Yu; Yangxin Wang; Wenqian Hao; Lin Wu; Yang Zhang; Hailong Shen; Yuhua Li; et al. (Food Chemistry, 2025)

Are root functional traits good predictors of wetland plant diversity and biomass under agricultural managements in a semi-arid region? - Mai Lv; Yifan Li; Mingye Zhang; Yu An; Shouzheng Tong; Haitao Wu (Ecological Complexity, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

A full sub-2 nm and acid-resistant MOF-COF ionic diode membrane for efficient ionic gradient power generation - Norman C.-R. Chen; Po-Chun Han; Li-Hsien Yeh; Yu-Hsiang Peng; Chia-An Lung; Yusuke Yamauchi; Kevin C.-W. Wu (Chemical Engineering Journal, 2025)

Elucidation of the biodegradation pathways of polyurethane and polyethylene terephthalate by a Fusarium strain enriched from soil-plant systems - Eyalira Jacob Okal; Yanfei Wu; Shahid Iqbal; Zhaorui Liu; Yuwei Hu; Na Hu; Tingfang Zhong; Jingxian Li; Dongmei Yu; Bishal Gurung; Dong Liu; Peter Mortimer; et al. (Bioresource Technology, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Dietary Supplementation with Multi-strain Probiotic Formulation (Bifidobacterium B8101, Lactobacillus L8603, Saccharomyces bayanus S9308, and Enterococcus SF9301), Betaine or their Combination Promotes Growth Performance Via Improving Intestinal Development in Broilers - Dan Hu; Xiaoting Wu; Pin Song; Manman Hou; Li’an Pan; Xiaoran Yang; Qinwei Sun; Yingdong Ni (Probiotics and Antimicrobial Proteins, 2025)

PatchTST-DME: Frequency-Aware Transformer for Potato Price Forecasting in Agricultural Management - An Zhang; Sheng Chen; Chao Wu; Guiyuan Li; Li Liu (Potato Research, 2025)

Integrated controls of soil and vegetation dynamics on soil organic and inorganic carbon covariation in grazed alpine wetlands - Yifan Li; Mingye Zhang; Yu An; Le Wang; Xianglong Xing; Shouzheng Tong; Haitao Wu; Ming Jiang; Kaishan Song (Plant and Soil, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Effects of Agricultural Drainage on Plant Community in Bolboschoenus planiculmis Wetlands in Songnen Plain, China - Yu An; Weimin Li; Le Wang; Bo Liu; Keke Shi; Yifan Li; Xuan Wang; Haitao Wu; Shouzheng Tong (Chinese Geographical Science, 2025)

Full-length genome sequence of Magnaporthe oryzae botourmiavirus 13 - Yuxin Wu; Miaomiao Chen; Cong Li; Xinyi Li; Guolin Zhang; Hongliu An; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2025)

Synergistic effect of two complementary acceptors assists high-efficiency as-cast organic solar cells - Mengyun Jiang; Bao Zhang; Peng Mao; Qian Guo; Yingqi Wang; Jiawei Qiao; Tao Zhang; Yongmin Luo; Quansong Li; Xiaotao Hao; Jianhui Hou; Jiaying Wu; et al. (Science Bulletin, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Characterizing three-dimensional spatiotemporal dynamics of flash drought across three contrasting climate regimes in China - Jiayun Li; Chuanhao Wu; Pat J.-F. Yeh; Chuan-An Xia; Weili Liu; Jiali Ju; Jun Zhou; Bill X. Hu; Shanshui Yuan; Wenhan Lv; Guoru Huang; Yong Lei (Journal of Hydrology, 2025)

Engineered Plasmonic multi-hot spots on magnetic Nanospheres for quantitative detection of pesticide residues on food surfaces via SERS tagging analysis - Ming-Jie Wan; Yu-Ting Wu; Yan-Hui Wang; Xiao-Hang Wu; En-Ming You; An Wang; Sheng-Hong Liu; Jin-Chao Chen; Yue-Jiao Zhang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Excessive health risks of summer aerosol sources related to particle-bound toxic metals in the Tibetan Plateau, China - Jiwei Li; Yunfei Wu; Zhaoze Deng; Liang Ran; Yunjie Xia; Jianchun Bian; Renjian Zhang; Yang Yu; Jiutao An (Environmental Pollution, 2025)

Unexpected benefits of agricultural greenhouses in mitigating ozone pollution on crop yields in China - Jingwei Zhang; Yuanqi Huang; Xiaoye Tong; Hailin Wu; Haiyan Ran; Wenxuan Fan; Yuanzhe Li; Shijing Dong; Shengsen Zhou; Jiangping Liu; Dawei Lu; Huizhi Liu; et al. (Atmospheric Environment, 2025)

Androgen induces 3′UTR shortening of de novo lipogenesis genes by alternative polyadenylation in prostate cancer cells - Wei-Jie Sun; Fei Liang; Hui Zhao; Yun-Mei Wang; Zhong-Yin Zhou; Hui Xu; Hang Liu; Dong Tang; An-Long Xu; Yong-Gui Fu; Xi Li; Jun Ouyang; et al. (Science China Life Sciences, 2025)
Alternative polyadenylation (APA) is a pervasive mechanism that is emerging as a formidable player in post-transcriptional regulation. The transcriptional landscape can be altered via APA in response to various stimulating factors. Using the PacBio single-molecule long-read sequencing method, we present for the first time the 3′UTR landscape and reveal a global increase of APA events in prostate cancer (PCa) LNCaP cells in response to androgen dihydrotestosterone (DHT), a critical regulator of PCa progression. With evidence from differential gene expression analyses of Illumina RNA-sequencing data, we demonstrated that genes with DHT-induced changes in both expression and APA were enriched in lipid metabolism. These genes predominantly supported de novo fatty acid synthesis, such as FASN and ACSL3 . Furthermore, we showed that an isoform switch to the proximal poly(A) site of these genes depended on the androgen receptor, and the expression of cancer-associated genes was upregulated by the escape of miRNA-regulated repression machinery. To address the role of key gene shortening in PCa, we prepared 22RV1-FS cells missing the distal poly(A) signal of FASN in the AR + PCa cell line 22RV1 using CRISPR/Cas9 technology. As expected, the edited 22RV1-FS cells overexpressed FASN mRNA and protein and were inclined to cell proliferation in vitro and tumorigenesis in vivo . Interestingly, we found that FASN transcripts with a shortened 3′UTR were significantly increased in advanced PCa and castration-resistant prostate cancer compared with benign prostate hyperplasia, suggesting a possible association between usage of the proximal poly(A) site and disease progression. Therefore, our study highlights the importance of the APA mechanism in response to DHT stimulation in PCa cells and provides a novel regulatory mechanism through which DHT-induced APA causes altered expression of de novo lipogenesis genes, with a possible association with the progression of PCa.

Optimizing seed filling performance of the double-filling air suction maize and soybean seed metering device based on DEM-CFD coupling method - Weiwei Wang; Lanzhou Song; Xue An; Longzhe Quan; Dongbo Xie; Yongxin Chen; Zhaodong Li; Zhenchao Wu; Liqing Chen (Computers and Electronics in Agriculture, 2025)

Gentamicin aggravates renal injury by affecting mitochondrial dynamics, altering renal transporters expression, and exacerbating apoptosis - Mingkang Zhang; Yan Zhou; Xiujuan Wang; Yile Li; Xin’an Wu (Toxicology Letters, 2025)

Selective growth of (5, 4) single-walled carbon nanotubes - Qianru Wu; Xueting Zhang; Hao An; Liu Qian; Linhai Li; Huaping Liu; Jiayang Zhang; Lili Zhang; Lianming Tong; Maoshuai He; Chang Liu; Feng Ding; et al. (Science Bulletin, 2025)

Opening of South China Sea in the Western Pacific forcing the climate cooling and lake level rise at Eocene–Oligocene transition - Jing Guo; Fujie Jiang; Guangrong Peng; Yuqi Wu; Weibing Shen; Rui Zhang; Yu An; Dapeng Jiang; Fusheng Yu; Yaqi Li; Zhifeng Yu; Jiabing Jiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Membrane-based processes for sustainable geothermal water reuse and mining: A comprehensive review of process integration and influencing parameters - Bing Wu; Tian Li; An Ding (Journal of Environmental Chemical Engineering, 2025)

Effect of the roasting process on the flavor formation of Tibetan pork: Matrices oxidation dependence on temperature or time - Qia Wang; Lujie Cheng; Yingmei Wu; Yingqun Wu; Qisen Xiang; Xiefei Li; Fengping An; Hongbo Song; Xin Li; Yuting Tian; Qun Huang (Food Chemistry, 2025)

Black carp STAT2 enhances IRF3-mediated antiviral signaling by regulating its ubiquitination and improving its nuclear translocation - Yiru Huang; Xinyu Wang; Jinyi Li; Ting Li; Xiaoyu Liu; Ji Liu; Jun Xiao; Hui Wu; Yong'an Zhang; Hao Feng (Fish & Shellfish Immunology, 2025)

Impact of per- and polyfluoroalkyl substances exposure on renal dysfunction: Integrating epidemiological evidence with mechanistic insights - Weitao Su; Ziwen An; Yayuan Mei; Zhenzhen Tan; Zexuan Jiang; Xiuli Zeng; Zhiqiang Dong; Ming Yang; Jingtao Wu; Huicai Guo; Ang Li (Environmental Pollution, 2025)

Charge-engineered biomass enables concurrent salt rejection and antibacterial performance toward efficient and sustainable interfacial solar desalination - Fengbo Zhu; Ke Qian; Fukai Li; Jianhang Zhao; Peng Yan; Meng An; Qiang Zheng; Zi Liang Wu; Wenwen Yu (Chemical Engineering Journal, 2025)

Insight into transformation of phosphorus species in biomass gasification at different stages - Xuemei Fu; Beibei Yan; Jian Li; Yanshan Wang; Xiaoqiang Cui; Guanyi Chen; Wenzhu Wu; Li’an Hou (Bioresource Technology, 2025)

Earthworm activity increases soil greenhouse gas emission and microbial biomass: a global meta-analysis - Yiqing Wang; Yuchen Zheng; Josep Peñuelas; Qiqian Wu; Yan Peng; Zimin Li; Petr Heděnec; Yuexin Fan; Chaoxiang Yuan; Jinghui He; Nannan An; Fuzhong Wu; et al. (Plant and Soil, 2025)

Critical factors and cost estimation for the immobilization of cadmium-contaminated paddy fields for rice safety - Shuqi Li; Dasong Lin; Lili Huo; Bo Wu; Lixia Sun; Yi An; Yuqing Xia (Journal of Soils and Sediments, 2025)

Integrating Attention Mechanisms in Graph Neural Networks for Marine Oil Spill Detection - Fengjing Cai; Yue Wang; Zhuangcai Tian; Xi’an Li; Jing Xu; Yuming Mo; Shaotong Zhang; Jinran Wu (Journal of Ocean University of China, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Spatiotemporal patterns of fecal cortisol metabolites in critically endangered wild Alpine musk deer in eastern edge regions of Tibetan Plateau: influencing factors and conservation implications - Jiayi Wu; Xiaoping Lu; Shuo Geng; Liquan Shen; Gong Wang; Rui Liu; Jun Qi; Chunting Feng; Junyi Yang; Zhengxu An; Rongxin Li; Na Qiao; et al. (Biologia, 2025)

Machine learning and network toxicology reveal arsenic as a key driver of non-carcinogenic health risks from heavy metal residues in Chinese medicinal plants - Guangying Du; Yuanju Zhang; Ting Zou; Chang Liu; Yingyue Hou; Jing Li; Feifei Deng; Jiayi An; Li Feng; Bangna Wu; Lingdan Huang; Ying Zhou (Science of The Total Environment, 2025)

Assessing and predicting hydro-biogeochemical dynamics in the Weihe River basin in a shifting climate - Guangchuang Zhang; Yiping Wu; Georgii Alexandrov; Huiwen Li; Xiaowei Yin; Xixi Lu; Fubo Zhao; Fan Wang; Linjing Qiu; Shuguang Liu; Ji Chen; Shantao An; et al. (Journal of Hydrology, 2025)

Transboundary conservation of musk deer (Moschus spp.): global synthesis of populations, distributions, threats, and recovery strategies - Xiaoping Lu; Shuo Geng; Junyi Yang; Jiayi Wu; Chunting Feng; Biqing Li; Rongxin Li; Zhengxu An; Achyut Aryal; Xiuxiang Meng (Journal for Nature Conservation, 2025)

Evolution of rock mass stress, movement, and deformation during injection-production processes in coal mines that have been converted into natural gas storage facilities - Xuejie Deng; Xiaoming Shi; Zhide Wu; Yuan An; Jichu Wang; Shicong Li; Xifeng Liang; Benjamin de Wit (Geomechanics for Energy and the Environment, 2025)

Fluorescence sensor based on layer-by-layer ligand self-assembled gold nanoclusters for on-site monitoring of chlorpyrifos - He Chen; Li An; Zhong Jin; Juan Zhou; Huan Ma; Jingwei Ma; Meng Li; Di Zhang; Lufei Zheng; Xujin Wu (Food Chemistry, 2025)

Strontium diorthovanadate anode for fast-charging lithium-ion battery with low redox potential - Xiaolei Li; Shuangdui Wu; Jian Su; Jing Zhang; Xuguang An; Weitang Yao; Hongli Sun; Borong Lin; Qingquan Kong (Chemical Engineering Journal, 2025)

The transcription factor BoMYC2 negatively regulates seed size by activating cytokinin dehydrogenase BoCKX5 in Broccoli - Xiaomei Wu; Yuxiao Tian; Weihuan Li; Jiaqing An; Zhijian Wu; Lu Huang; Junwei Wang; Zhenzhu Hu; Ke Huang; Qiuyun Wu (Theoretical and Applied Genetics, 2025)

Insight into the rutin biosynthesis in the unique flavonol synthesis pathway of Tartary buckwheat based on the enzymatic functions of FLSs - Chenglei Li; Jiayi Sun; Guanlan Shi; Xuerong Zhao; Jun Gu; Jiaqi Shi; Qihan Ma; Daoping Zeng; Tao Wang; Zizhong Tang; Tongliang Bu; Hui Chen; et al. (Theoretical and Applied Genetics, 2025)

Erratum to “Coupling of Sulfate Reduction and Dissolved Organic Carbon Degradation Accelerated by Microplastics in Blue Carbon Ecosystems” [Water Research, 279, (2025), 123414] - Heli Wang; Yin Zhong; Qian Yang; Jiaying Li; Dan Li; Junhong Wu; Sen Yang; Jiashuo Liu; Yirong Deng; Jianzhong Song; Ping'an Peng (Water Research, 2025)

Antidiabetic constituents of Kaempferiae rhizoma: Previously undescribed O-linked diarylheptanoid dimers promoting GLP-1 secretion via PKA-CREB pathway - Sheng-Li Wu; Tian Wang; Xin-Yu Li; Pianchou Gongpan; Xiao-Yan Huang; Yun-Bao Ma; Chang-An Geng (Phytochemistry, 2025)

The R2R3-MYB transcription factor MdMYB62 negatively regulates the drought and salt tolerance in apple - Xin-Long Guo; Xiang Wu; Hong-Liang Li; Ran-Xin Liu; Jian-Ping An; Chun-Xiang You (Journal of Plant Physiology, 2025)

Towards an isotope-based conceptual catchment model of the ecohydrological cycle in the Critical Zone on the Loess Plateau of China - Jinzhao Liu; Daniele Penna; Xiong Xiao; Li Guo; Guo Chen; Chong Jiang; Huawu Wu; Shengjie Wang; Zhiyun Jiang; Zhao Jin; Zhisheng An (Journal of Hydrology, 2025)

A reconstruction of Antarctic Sea ice extent since the 1950s from a snowpit methanesulfonate (MSA) record in East Antarctic inland - Jinhai Yu; Hongxi Pang; Guitao Shi; Wangbin Zhang; Shuangye Wu; Chunlei An; Yuansheng Li; Shugui Hou (Journal of Marine Systems, 2025)

Quantitatively tracing microplastics in sewage sludge using thermodesorption gas chromatography/mass spectrometry combined with pyrolysis - Zhixin Wu; Yuxuan Wu; Ziye Zhang; Jiao Dong; Huan Li; Xingru Zhao; Song Cui; Lihui AN (Journal of Hazardous Materials, 2025)

Emission characteristics of indoor HONO from residential natural gas cooking stoves in a household in Kunming, China - Hailin Wu; Haiyan Ran; Shijing Dong; Lingling Li; Jiangping Liu; Wenxuan Fan; Dawei Lu; Jingwei Zhang; Junling An (Journal of Hazardous Materials, 2025)

A stable all-solid-state lithium metal battery achieved by optimizing the cathode-electrolyte interface through perovskite-coating-stabilized single crystal LiNi0.9Co0.05Mn0.05O2 cathode - Cheng Liu; Wenjin Li; Kaiyuan Deng; Puxi An; Rui Wang; Beisen Chen; Qingmei Xiao; Jiatao Wu; Lei Yao; Guangliang Gary Liu (Chemical Engineering Journal, 2025)

Toward zero-waste phosphogypsum valorization: Reengineered reverse-direct flotation synchronizes gypsum purification and functional co-products production - Ming-Sheng Du; Bo Long; Yi-Zhe Mei; Yong-Shuang Li; Shuang Li; Xue-Qian Wu; Ru-an Chi; Yun-Zhi Tan; Dong-Sheng Li (Chemical Engineering Journal, 2025)

Three-step Merging of Daily Multi-satellite Rainfall Estimates Based on Probability Density Function Matching and Dynamic Bayesian Model Averaging - Yunyao Chen; Binquan Li; Maihuan Zhao; Tuantuan Zhang; Zhijun Wu; Xindai An (Water Resources Management, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Exogenous nitrogen enhances aboveground plant phosphorus accumulation through soil moisture and organic carbon in semi-arid grazed wetlands - Mingye Zhang; Shuchen Liu; Yu An; Dongjie Zhang; Jianghao Tan; Le Wang; Yifan Li; Ming Jiang; Haitao Wu; Shouzheng Tong (Agriculture, Ecosystems & Environment, 2025)

Coupling of sulfate reduction and dissolved organic carbon degradation accelerated by microplastics in blue carbon ecosystems - Heli Wang; Yin Zhong; Qian Yang; Jiaying Li; Dan Li; Junhong Wu; Sen Yang; Jiashuo Liu; Yirong Deng; Jianzhong Song; Ping'an Peng (Water Research, 2025)

Linaggrenoids A−I, structurally diverse lindenane sesquiterpenoids with anti-hepatic fibrosis effects from Lindera aggregata - Wen-Xian Li; Lu Gan; Yi-Ling Liao; Yu-Wei Wu; Bai-Hui Zhang; De-an Guo; Wei Li (Phytochemistry, 2025)

A preliminary investigation of pore development mechanisms in highly matured solid bitumen: Implications from the Ediacaran Dengying Formation solid bitumen in the central Sichuan Basin, Southwest China - Lianqiang Zhu; Hui Tian; Peng Cheng; Haifeng Gai; Tengfei Li; Qin Zhou; Wei Wu; Chao Luo; Ping'an Peng (Marine and Petroleum Geology, 2025)

Electronic state reconfiguration of NiMoCox boosts electrocatalytic upcycling of polyethylene terephthalate plastic wastes for simultaneous production of formate and green hydrogen - Shaofeng Wang; Shuaidong Li; Yutong Li; Yue Xu; Zhaomeng Wu; Yingjian He; Yongwei Zhao; Zheer An; Ying Lan; Yanxiao Hu; Jingzi Zhang; Yan Huang; et al. (Chemical Engineering Journal, 2025)

Elucidating the Varied Characteristics of Compound Hot–Drought From Two Distinctive Extreme Events in the Yangtze River Valley - An Xuehua; Sun Shanlei; Ma Qianrong; Wu Hao; Li Daiyuan; Wu Wei (International Journal of Climatology, 2025)
Compound hot‐drought events exert profound impacts on ecosystems, agriculture and public health, highlighting the need to understand their characteristics and driving mechanisms for effective climate change mitigation and adaptation strategies. This study reveals that the severity of summer hot–drought events in the Yangtze River Valley (YRV) significantly increased during 1961–2022. Among these, 2013 and 2022 represent two distinct types of hot‐drought events: High‐temperature and both high‐temperature and deficient precipitation dominated. In both years, the eastward expansion of the South Asian High and the westward extension of the Western Pacific Subtropical High established persistent high‐pressure systems over the YRV. In 2013, cooler sea surface temperature (SST) anomalies in the Northwestern Indian Ocean promoted the anomalous westerly, reducing the southwest water vapour transport to the region. Concurrently, the Western North Pacific anticyclone (WNPAC) positioned over the East China Sea facilitated limited moisture inflow from the Pacific. This configuration, mainly governed by persistent high‐pressure systems, resulted in high‐temperature‐dominated compound events. In contrast, the 2022 event displayed greater complexity. Warmer SST anomalies in the Bay of Bengal intensified convective activity, enhancing the local Hadley circulation and promoting descending motion over the YRV. Strengthened easterly, influenced by the Matsuno–Gill response, contributed to the westward extension of the WNPAC and altered tropical water vapour transport, causing pronounced tropospheric descent and moisture deficits over the YRV. Negative tropospheric potential vorticity anomalies further exacerbated the compound event through land‐atmosphere interactions, including scarce precipitation, soil drying and increased surface sensible heat flux. Consequently, the 2022 event was more severe and multifaceted than that in 2013.

Impacts of grazing intensity on soil properties and carbon content in Xilamuren Grassland - Xu Li; Chunchun An; Xiaoqian Li; Qicong Wu; Xinchuang Chen; Jianying Guo; Tianming Gao; Huaichang Wang; Zhi Dong (Journal of Environmental Management, 2025)

Study of enhanced nitrogen removal performance and mechanism of iron-modified activated carbon in low-temperature environments - Guangtao Li; Jinlong Han; Yunchang Wang; Shihong Wu; Liyan Ge; Xueqian An; Xiaoyang Liu; Wenfang Gao; Li Sun; Zhijun Ren; Kengo Kubota (Journal of Environmental Chemical Engineering, 2025)

Water vapor absorption peaks in infrared spectroscopic gas logging and correlation with water layers - Xiaoshan Li; Xiaojun Tang; Zijian Huang; Liwei Wu; Mingyu Guo; Youshui Lu; Tongrui An; Zeyu Zhang; Chongzhi Liu; Houqing Chen; Tong Wu (Gas Science and Engineering, 2025)

Identification and taste presentation characteristics of umami peptides from soybean paste based on peptidomics and virtual screening - Guoyang Pan; Feiyu An; Junrui Wu; Yaqi Wang; Li Deng; Xing Tong; Shuaiqi Ji; Jinhui Jiang; Qu Liu; Ning Yang; Dongbing Tao; Rina Wu (Food Chemistry, 2025)

Corrigendum to “Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration” [Chem. Eng. J. 497 (2024) 154433] - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2025)

Pilot-scale rotor device with low acid-site zeolite for rapid adsorption–desorption of polymerizable VOCs - Huifang Wu; Wenjing Zhang; Lisha Miao; Kan Li; Haoxuan Liu; Weili Zhu; Zeyao An; Yanfeng Tang; Lizhong Liu; Jinping Jia (Chemical Engineering Journal, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

2,4,6-trinitrotoluene induces neurotoxicity by affecting the G protein pathways in Caenorhabditis elegans - Ying Li; Yanping Zhou; Chunyan Wang; Yaguang Nie; Yongbing Zhu; Sanping Zhao; Lijun Wu; An Xu (NeuroToxicology, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Widely targeted metabolomics analysis flavonoid metabolites in different purple teas - Qing Wang; Dandan Qin; Erdong Ni; Kaixing Fang; Qiushuang Wang; Hongjian Li; Jian-an Huang; Zhonghua Liu; Hualing Wu (Food Chemistry, 2025)

Unravelling degradation mechanisms of anion exchange membrane direct ammonia fuel cells via distribution of relaxation times - Wenzhi Li; Qing Wang; Yun Liu; Lizhen Wu; Zhefei Pan; Rong Chen; Liang An (Chemical Engineering Journal, 2025)

The strong metal-support interaction regulation on cathode–anode coupling catalysts to boost the pollutant degradation - Chuanshun Feng; Qicheng Zhang; Xiuyu Loh; Shuo Chen; Jiawen Wu; An Cai; Bin Chen; Jijie Zhang; Xiaobin Fan; Wenchao Peng; Yang Li (Chemical Engineering Journal, 2025)

Molecular characterization of a novel gammascleroulivirus from the rice blast fungus Magnaporthe oryzae isolate ES155 - Cong Li; Yuxin Wu; Xinyi Li; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Archives of Virology, 2025)

Comparative mitogenomes of Amblyopinae (Gobiiformes: Gobionellidae) and freshwater adaptation in Taenioides sp. - Li Gong; Kaixin Wang; Tianwei Liu; An Xu; Nannan Zhang; Wenchao Wu; Liqin Liu; Jing Liu; Fenghui Li; Zhenming Lü (Acta Oceanologica Sinica, 2025)

A cross-sectional survey of international voyage ships entering Zhoushan Port by sea, Zhoushan, 2020-2022 - Yuzhe Hua; Yaxin Dai; Jingping Yi; Wenjie Wu; Peng Li; Kefeng Li; Wei Chen; An Tang (Frontiers in Marine Science, 2025)
Crew members aboard international voyage ships are susceptible to imported acute respiratory infections, leading to clusters of outbreaks that pose challenges to the health of crew members. The aim of the proposed study was to optimize a plan for the quarantine process and rescue measures in response to a coronavirus disease 2019 (COVID-19) outbreak at sea to provide policy guidance for the prevention and control of severe infectious diseases on international voyage ships. Here, we described the baseline characteristics of international voyage ships and crew members entering Zhoushan Port from 2020 to 2022 and analyzed the factors influencing the incidence rate of COVID-19 among crew members. There were 161 COVID-19 cases among cargo ships entering Zhoushan Port by sea, with an average incidence rate of 16.00% (95% CI: 13.73%–18.27%). The incidence rate of COVID-19 was significantly higher among crew members with replacement, long voyage, and those who stayed at multiple anchorages or stayed for a long time. The risk of COVID-19 infection for crew members staying at more than 4 anchorage was the highest, which was 2.667 (95% CI: 1.857–3.830) times that of crew members staying at less than 4 anchorage. We developed and refined the workflow for a public health assistance plan for outbreaks at sea on the basis of our experience with several COVID-19 outbreaks on international voyage ships. The workflow includes fundamental requirements, sampling and testing methods, personnel transfer procedures, medical waste disposal guidelines, and disinfection procedures for affected ships. Our public health assistance plan can be applied to other international voyage ships for which urgent public health assistance is needed during sudden infectious disease outbreaks.

Odor impact patterns and health risks of various enterprises in the rubber product manufacturing industry - Yan Zhang; Yan Zhao; Li’an Hou; Zhiyang Zhang; Kehua Zou; Gen Wang; Zhiqiang Lu; Huanwen Cui; Jie Meng; Ting Wu; Jing Wang; Zengxiu Zhai (Journal of Hazardous Materials, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Unraveling the origin of Pd nanoparticles supported N–doped biochar derived from spent coffee ground for enhanced Suzuki coupling reaction activity - Hongwei He; Shuya Zhang; Jiawen Wu; An Cai; Zhoulin Ma; Luping Shen; Xingjin Zhang; Xiaobin Fan; Wenchao Peng; Yang Li (Journal of Environmental Chemical Engineering, 2025)

Combined effects of microplastics and flupyradifurone on gut microbiota and oxidative status of honeybees (Apis mellifera L.) - Tong An; Wangjiang Feng; Han Li; Yanyan Wu; Pingli Dai; Yong-Jun Liu (Environmental Research, 2025)

Correction: The complete genomic sequence of Magnaporthe oryzae polymycovirus 1 - Hong Zheng; Cong Li; Yuxin Wu; Xinyi Li; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Virus Genes, 2025)

The complete genomic sequence of Magnaporthe oryzae polymycovirus 1 - Hong Zheng; Cong Li; Yuxin Wu; Xinyi Li; Hongliu An; Shouguo Fang; Songbai Zhang; Qingchao Deng (Virus Genes, 2025)

Synergies and trade-offs between aboveground and belowground traits explain the dynamics of soil organic carbon and nitrogen in wetlands undergoing agricultural management changes in semi-arid regions - Yu An; Le Wang; Mingye Zhang; Shouzheng Tong; Yifan Li; Haitao Wu; Ming Jiang; Xuan Wang; Yue Guo; Li Jiang (Agriculture, Ecosystems & Environment, 2025)

Provenance evolution and drainage reorganization during tectonic inversion of a continental rift basin: Detrital zircon evidence from the Late Cretaceous Songliao Basin, NE China - Zhengxuan Wu; Yuan Gao; Dongzhao An; Liangliang Zhang; Mingang Hao; Yuyin Li (Cretaceous Research, 2025)

Screening of Spinal Muscular Atrophy Carriers and Prenatal Diagnosis in Pregnant Women in Yancheng, China - Huilin Sun; Jianli Zheng; Qing’e Zhang; Feifei Ying; Yadong Fu; Yongjuan Guan; Jing Wu; Yueyun Zhou; Jingjing Dong; Mengjun Xu; Fangfang Yang; Ning An; et al. (Biochemical Genetics, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Impact of coking plant to heavy metal characteristics in groundwater of surrounding areas: Spatial distribution, source apportionment and risk assessments - Congqing Wang; Wanjun Wang; Chao Wang; Shixing Ren; Yingjun Wu; Meicheng Wen; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2025)

Comparative analysis of fecundity related traits and transcriptome in two isofemale lines of the egg parasitoid, Trichogramma dendrolimi (Matsumura) - Hong-Yu Liang; An-Ke Liu; Ning He; Jin-Cheng Zhou; Xiao-Hui Ma; Li-Sheng Zhang; Wu-Nan Che; Hui Dong (Journal of Asia-Pacific Entomology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Investigation of water retention and volumetric deformation characteristics of soils subjected to wetting–drying cycles - Shujian Wang; Yiyi Liu; Chuanshan Wu; Yixin Li; Ronghua Zhang; Senlin An; Hongguang Jiang; Zhanyong Yao (Bulletin of Engineering Geology and the Environment, 2025)

Enhancing Aerodynamic Performance of Horizontal Axis Wind Turbine Blade Aerodynamic Performance Under Rough Wall Condition Using Vortex Generators - Yingjian Yang; Dian Wang; Hairui Zhang; Rongyu Zha; Guangxing Wu; Chang Cai; Jianhua Zhang; Qing’an Li (Journal of Marine Science and Engineering, 2025)
In the complex and harsh working environment of wind turbines, the horizontal axis wind turbine blade is increasingly confronted with the issue of surface roughening. It leads to a decrease and instability in the output power of the horizontal axis wind turbine. Vortex generator have emerged as a potential solution to this problem by regulating the flow patterns on the blade surface. This research focuses on exploring the impact of vortex generator on the aerodynamic performance of blades under rough wall condition by wind tunnel experiment and computational fluid dynamics simulation. It is important to improve the aerodynamic performance of horizontal axis wind turbine under rough condition. The results show that vortex generator changes the airfoil aerodynamic performance by slowing the stall angle of attack and increasing the ratio of lift-drag in some angles of attack. vortex generator delays the flow separation of the suction surface under the rough wall condition. It is able to counteract the reduction in the aerodynamic performance of blade under rough wall condition. At tip speed ratio is 5.83, vortex generator increased power coefficient by 47.8% under rough wall condition by reducing the flow separation area of 33% radius and weakening the spanwise flow. The study found that the vortex generator effectively eliminated the negative effects of blade surface roughening on aerodynamic performance, improved the roughness insensitivity of the blade, and has good potential for future applications.

Warming effects on pelagic carbon metabolism is related to substrate composition and bacterioplankton community history - Zhendu Mao; Yixuan Han; Fan Xun; Shilin An; Biao Li; Yujing Wang; He Chen; Qinglong L. Wu; Peng Xing (Water Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Unraveling the role of V modified CoO in a wide pH range Fenton-like process - Xiaoyi Huang; Qiangqiang Wu; Jingwen Tang; Rongsheng Ning; Jiang Yuan; Shengqiong Fang; Shuili Yu; Li'an Hou; Qinglun You (Journal of Environmental Management, 2025)

Metagenomics reveals the resistance patterns of electrochemically treated erythromycin fermentation residue - Jieya Zhou; Hao Wu; Haiyan Wang; Zongru Wu; Lihu Shi; Shulei Tian; Li-an Hou (Journal of Environmental Sciences, 2025)

Controllable synthesis of Pt-rich shell/Mx core [M = Ni, Fe, Co] metal aerogels as efficient electrocatalysts for hydrogen evolution reaction - Wenliu Wu; Cuihua An; Zhiwei Li; Hassanien Gomaa; Shuang Chen; Chunling Qin; Qibo Deng; Kai Zhang; Ning Hu (Fuel, 2025)

Genetic diversity analysis and DNA fingerprinting of primary Qingke (Hordeum vulgare L. var. nudum Hook. f.) cultivars - Qian Hu; Youhua Yao; Yongmei Cui; Xin Li; Likun An; Yixiong Bai; Baojun Ding; Xiaohua Yao; Kunlun Wu (Genetic Resources and Crop Evolution, 2025)
To assess the genetic diversity of the primary Qingke cultivars and establish their unique genetic profiles, 837 barley simple sequence repeat (SSR) primers were screened across 12 cultivars. The selection process involved the utilization of polyacrylamide gel electrophoresis and capillary electrophoresis technology, to identify primers exhibiting desirable characteristics, such as polymorphism, stability, and reproducibility. Subsequently, we analyzed the genetic diversity of the primary Qingke cultivars to for DNA fingerprints. A total of 18 pairs of SSR markers were selected as the optimal markers for constructing fingerprints of major Qingke cultivars. These included 83 observed alleles (N a ), ranging from there to 11, with an average of 4.61 per pair. Notably, Bmag0496 and Scssr04163 exhibited higher allelic diversity, with 11 and 8 loci, respectively. The polymorphism information content (PIC) ranged from 0.36 to 0.74, with an average of 0.52. The expected heterozygosity (H e ) ranged from 0.4031 to 0.7682, with an average of 0.59, and the observed heterozygosity (H o ) varied between 0.13 and 0.67, with an average of 0.32. The outcomes obtained through phylogenetic tree analysis, population structure assessment and principal component analysis demonstrated that the primary Qingke cultivars could be classified into three distinct groups: group I primarily originated from Xizang and Qinghai provinces; group II mainly consisted of cultivars from Yunnan and Heilongjiang provinces; and group III predominantly comprised cultivars originating from Qinghai and Gansu provinces. Interestingly, the Sichuan cultivars were distributed across all three groups without any clear tendency toward a specific cluster or subgroup. These findings indicated that the genetic distance among Qingke cultivars was significantly correlated with geographic location but not exclusively determined by it. The construction of DNA fingerprints for the primary Qingke cultivars used these identified sets of SSR primers (18 pairs) laid a solid foundation for cultivar identification, conservation and utilization efforts related to this crop.

Macrophyte Restoration Promotes Lake Microbial Carbon Pump to Enhance Aquatic Carbon Sequestration - He Chen; Peng Xing; Shuhji Kao; Shilin An; Zhendu Mao; Shiming Fan; Biao Li; Qingyun Yan; Qinglong L. Wu (Global Change Biology, 2025)
Macrophyte‐based lake restoration has successfully transitioned lakes from turbid conditions dominated by phytoplankton to a more natural, clear state; however, its impact on microbial carbon pump‐mediated dissolved organic carbon (DOM) storage and greenhouse gas (GHG) emissions in the aquatic ecosystem remains largely unexplored. Through a year‐long field study, we conducted a comparative analysis of two alternative habitats within the same lake—restored and unrestored areas. Results demonstrated that restoration not only substantially decreases nutrient levels and algal blooms—evidenced by over 50% reductions in nitrogen, phosphorus, and chlorophyll a—but also significantly increases the accumulation of recalcitrant DOM. This is characterized by rises of 9.52% in highly unsaturated compounds, 8.68% in carboxyl‐rich alicyclic molecules, 37.54% polycyclic condensed aromatics and polyphenols, and 20.21% in SUVA 254 . Additionallly, key microbial taxa with potent carbon pump functions—primarily Gammaproteobacteria, Alphaproteobacteria, and Actinobacteria—are enriched in restored areas. Structural equation modeling (SEM) further elucidated the complex interrelationships within more pristine lake ecosystems: macrophytes and elevated dissolved oxygen (DO) concentrations enhance carbon sequestration via microbial carbon pump pathways, while the restoration significantly mitigates methane emissions caused by eutrophication. These findings highlight an extra function of aquatic macrophyte restoration, offering valuable insights into microbial processes for future restoration efforts aimed at promoting sustainable aquatic ecosystems and mitigating global warming.

Transcriptome and pathophysiological analysis during Bacillus cereus group infection in Pelodiscus sinensis uncovered the importance of iron and toll like receptor pathway - Li-Wu Cheng; Qiong-Yi Huang; Pei-Chi Wang; Ming-An Tsai; Shih-Chu Chen (Aquaculture, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Assessment of internal exposure risk from metals pollution of occupational and non-occupational populations around a non-ferrous metal smelting plant - Yingjun Wu; Mengdie Qi; Hang Yu; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2025)

3D hot spot construction on the hydrophobic interface with SERS tags for quantitative detection of pesticide residues on food surface - Yan-Hui Wang; Chen Huang; Xiao Wu; Xiao-Feng Liu; En-Ming You; Sheng-Hong Liu; An Wang; Shangzhong Jin; Fan-Li Zhang (Food Chemistry, 2025)

Using chondroitin sulfate lithium hydrogel for diabetic bone regeneration via regulation of macrophage polarization - Chenci Xu; Weiqi Li; Jing Mao; Ziyang Liu; An Lao; Lixia Mao; Anqi Gu; Jiaqing Wu; Aili Shen; Kaili Lin; Jiaqiang Liu (Carbohydrate Polymers, 2025)

The impacts of yaw attitude strategies for eclipsing GNSS satellites on precise point positioning time transfer - Lei Wang; Wenbin Shen; Lihong Li; An Ning; Kuangchao Wu; Wei Xu; Ziyu Shen (GPS Solutions, 2025)

Dietary Probiotic Rhodopseudomonas palustris Formulation Improves Growth Performance, Muscle Composition, Digestive Enzyme Activity, Non-Specific Immunity and Disease Resistance of Juvenile Ivory Shell (Babylonia areolata) - Xiao Wang; Yao-Peng Lu; Ze-Long Zhang; Pei-Hua Zheng; Jun-Tao Li; Xiu-Xia Zhang; Jia-Jun Li; Heng-Mei Wu; Jian-An Xian (Fishes, 2024)
Rhodopseudomonas palustris (RP) are known anaerobic bacteria with probiotic properties containing several bioactive compounds and enzymes that benefit aquatic animals. However, studies on the use of RP on aquatic animal species are limited. This study investigated the effects of dietary supplementation with RP formulation on the growth, non-specific immunity, and disease resistance of juvenile ivory shells (Babylonia areolata). The experiment was conducted for 8 weeks, with B. areolata fed a control diet (RP0) and four diets containing four different RP formulations, with doses of 1 (RP1), 5 (RP2), 10 (RP3), and 20 (RP4) g/kg, respectively. Higher levels of R. palustris in the formulation led to increased final weight, weight gain, and specific growth rate in B. areolata. The crude protein content was significantly higher in the RP4 group compared to the RP0 group. However, there was no significant difference in the crude lipid content. Higher levels of R. palustris in the RP4 formulation group increased the trypsin and lipase activities. Dietary supplementation with RP significantly increased the total antioxidant capacity, superoxide dismutase, and catalase activities and decreased the malondialdehyde content in B. areolata. Acid phosphatase and alkaline phosphatase activities were significantly increased in the RP4 group compared to the RP0 group. Dietary RP significantly increased the expression levels of antioxidant-related (superoxide dismutase, Cu/Zn-superoxide dismutase, glutathione S-transferase A-like, ferritin) and immune-related (acid phosphatase, cytochrome c) genes. Higher levels of R. palustris in the formulations RP3 and RP4 increased the survival rate of B. areolata challenged with Vibrio parahaemolyticus. These findings indicate that R. palustris preparation could improve growth performance, muscle composition, and digestive capacity and may act as an immune booster for preventing disease in B. areolata.

A Method for Aliasing Metal Particle Recognition Based on Three-Coil Sensor Using Frequency Conversion - Di Wu; Yucai Xie; Chenyong Wang; Xian’an Gu; Feng Gu; Guoqing Li; Hongpeng Zhang; Yunsheng An; Rui Li; Changzhi Gu (Journal of Marine Science and Engineering, 2024)
The diesel engine on a ship is crucial as it serves as the primary power source, significantly influencing both the vessel’s efficiency and safety. Monitoring metal wear particles found in lubricating oil is essential for assessing the lubrication condition of mechanical equipment onboard and anticipating potential failures. Analyzing these metal wear particles allows us to gauge the wear status of bearing pairs within the machinery, thereby providing a technical foundation for routine maintenance activities. However, under real operating conditions, it can be challenging to prevent multiple metal particles from simultaneously passing through sensors. To address this issue, this research introduces an innovative three-coil induction sensor that employs a variable-frequency excitation technique to explore how induction and eddy currents interact. The findings indicate that when the excitation frequency changes, the peak value of the signal from 337 μm iron particles only increases by 3.35 times, while the peak value of the signal from 340 μm copper particles increases by 22.69 times. Consequently, this study recommends using changes in excitation frequency to differentiate between mixed metal particles made of various materials.

Modeling urban expansion and its impacts on carbon storage through integrative scenario analysis for sustainable development in the Changchun-Jilin-Tumen region - Tong Wu; Mingqi An; Lulu Zhang; Xiaozheng Wu; Mingyu Li (Sustainable Cities and Society, 2024)

Development of an efficient and Reproducible in vitro regeneration and transformation protocol for Luffa cylindrica (L.) Roem - Zhengjing Wu; Chenfang Li; Yidian Gao; Hao Zhang; Yuan Long; Bingjie An; Sujuan Liu; Jingjing Wu (South African Journal of Botany, 2024)

Remediation of Cd-As-Ni co-contaminated soil by extracellular polymeric substances from Bacillus subtilis: Dynamic improvements of soil properties and ecotoxicity - Yang Li; Lei Cheng; Baolin Yang; Yanan Zhao; Yuting Ding; Chenxi Zhou; Yuanyuan Wu; Ruoyun Dong; Yun Liu; An Xu (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Nephropathy induced by cisplatin results from mitochondrial disruption, impaired energy metabolism, altered expression of renal transporters, and accumulation of urinary toxins - Mingkang Zhang; Jianping Zhang; Yanrong Ma; Yongwen Jin; Yile Li; Xin’an Wu (Journal of Trace Elements in Medicine and Biology, 2024)

Concurrent ozone and high temperature exacerbates nasal epithelial barrier damage in allergic rhinitis mice: Insights from the nasal transcriptome and nasal microbiota - Juan Li; Huai Wei; Ning Wang; Jing Chen; Weiping Zhang; Zhen An; Jie Song; Yixuan Liang; Xiaowan Liu; Weidong Wu (Journal of Hazardous Materials, 2024)

Hierarchical nanoarchitectonics of hollow hexanitrostilbene (HNS) microspheres to improve safety and combustion performance - Yi Liu; Jiani Xie; Yunyan Guo; Jiawei Li; Kai Han; Linchong Xu; Chongwei An; Zhongliang Ma; Bidong Wu (Fuel, 2024)

CFD-DEM study on the raceway transport phenomena and thermo-chemical behaviors in a three-dimensional blast furnace: Effects of process parameters - Meng Li; Zhong Li; Chao Li; Guanyin Wu; Xizhong An; Hao Zhang; Haitao Fu; Xiaohong Yang; Qingchuan Zou (Fuel, 2024)

Green fabrication of modified lignin/zeolite/chitosan-based composite membranes for preservation of perishable foods - Zhan-Chao Li; Meng-Yao Su; Xiao-Yu Yuan; Hai-Qing Lv; Rui Feng; Li-Jie Wu; Xiao-Ping Gao; Yan-Xia An; Zhan-Wei Li; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Chemistry, 2024)

Microfluidic-blow-spinning of carvacrol-loaded porphyrin metal − organic framework nanofiber films with synergistic antibacterial capabilities for food packaging - Zi-An Deng; Menglu Wu; Chaoyi Shen; Xiangzheng Yang; Da Wang; Jiangkuo Li; Di Wu; Kunsong Chen (Food Chemistry, 2024)

Unlocking superior preservation: The synergy of lignin and zeolite in chitosan-based composite films for perishable foods - Zhan-Chao Li; Xi Chen; Jia-Li Zhang; Xiao-Ping Gao; Yan-Xia An; Li-Jie Wu; Miao-Yun Li; Gai-Ming Zhao; Xiao-Peng Wang (Food Packaging and Shelf Life, 2024)

Mitochondrial dysfunction induced by ambient fine particulate matter and potential mechanisms - Zhen An; Guangyong Liu; Lingling Shen; Yongmei Qi; Qinan Hu; Jie Song; Juan Li; Jinge Du; Yichun Bai; Weidong Wu (Environmental Research, 2024)

Probabilistic quantile multiple fourier feature network for lake temperature forecasting: incorporating pinball loss for uncertainty estimation - Siyuan Liu; Jiaxin Deng; Jin Yuan; Weide Li; Xi’an Li; Jing Xu; Shaotong Zhang; Jinran Wu; You-Gan Wang (Earth Science Informatics, 2024)
Lake temperature forecasting is crucial for understanding and mitigating climate change impacts on aquatic ecosystems. The meteorological time series data and their relationship have a high degree of complexity and uncertainty, making it difficult to predict lake temperatures. In this study, we propose a novel approach, Probabilistic Quantile Multiple Fourier Feature Network (QMFFNet), for accurate lake temperature prediction in Qinghai Lake. Utilizing only time series data, our model offers practical and efficient forecasting without the need for additional variables. Our approach integrates quantile loss instead of L2-Norm, enabling probabilistic temperature forecasts as probability distributions. This unique feature quantifies uncertainty, aiding decision-making and risk assessment. Extensive experiments demonstrate the method’s superiority over conventional models, enhancing predictive accuracy and providing reliable uncertainty estimates. This makes our approach a powerful tool for climate research and ecological management in lake temperature forecasting. Innovations in probabilistic forecasting and uncertainty estimation contribute to better climate impact understanding and adaptation in Qinghai Lake and global aquatic systems.

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Calcium chloride seed priming: A dual-action strategy for enhancing Cyrtorhinus lividipennis attraction and deterring brown planthopper infestations in rice - Zhong-Yan Zhu; Xiao-Bao Wu; Jia-jia An; Qian-Qian Deng; Jun Wang; Li-Na Chen; Mao Ye (Crop Protection, 2024)

Long-term exposure to low-level ozone and the risk of hypertension: A prospective cohort study conducted in a low-pollution region of southwestern China - Fuyan Zhang; Ziyun Wang; Ling Li; Xu Su; Yuandong Hu; Yu Du; Qingqing Zhan; Tianlin Zhang; Qinyu An; Tao Liu; Yanli Wu (Science of The Total Environment, 2024)

Microbial fertilizers improve soil quality and crop yield in coastal saline soils by regulating soil bacterial and fungal community structure - Qicong Wu; Yang Chen; Xiaohui Dou; Dongxi Liao; Kaiyi Li; Chunchun An; Guohui Li; Zhi Dong (Science of The Total Environment, 2024)

Assessment of thermal power plant CO2 emissions quantification performance and uncertainty of measurements by ground-based remote sensing - Chao Li; Xianhua Wang; Hanhan Ye; Shichao Wu; Hailiang Shi; Yuan An; Erchang Sun (Environmental Pollution, 2024)

Co-emissions of fluoride ion, fluorinated greenhouse gases, and per- and polyfluoroalkyl substances (PFAS) from different fluorochemical production processes - Zian Liang; Yonglong Lu; Zhiwei Cao; Xinyi Huang; Haojie Lei; Jialong Li; Zhaoyang Wu; Xupeng An; Pei Wang (Environmental Pollution, 2024)

Ozone-Induced Lung Injury are Mediated Via PPAR-Mediated Ferroptosis in Mice - Juan Li; Huai Wei; Ning Wang; Jing Chen; Ying Zhang; Zhen An; Jie Song; Tianqi Niu; Weidong Wu (Biological Trace Element Research, 2024)

Hazards of toxic metal(loid)s: Exploring the ecological and health risk in soil–crops systems with long-term sewage sludge application - Shitao Gao; Yanmei Dong; Qingqi Jia; Shuxia Wu; Jiayun Bai; Chao Cui; Ying Li; Peng Zou; Miaoying An; Xinzhong Du; Hongbin Liu (Science of The Total Environment, 2024)

Sustainable development of cutting fluids: The comprehensive review of vegetable oil - Xiangcheng Luo; Shujing Wu; Dazhong Wang; Yixin Yun; Qinglong An; Changhe Li (Journal of Cleaner Production, 2024)

Widely metabolomic combined with transcriptome analysis to build a bioactive compound regulatory network for the fruit growth cycle in Pseudocydonia sinensis - Shuangyu Zhang; Yang Wu; Yanshen Ren; Yaping Xu; Hong An; Qianyi Zhao; Yu Wang; Houhua Li (Food Chemistry, 2024)

The toxicity of cisplatin derives from effects on renal organic ion transporters expression and serum endogenous substance levels - Mingkang Zhang; Yile Li; Yanrong Ma; Yongwen Jin; Xueyan Gou; Yufan Yuan; Fen Xu; Xin'an Wu (Food and Chemical Toxicology, 2024)

Chronic PM2.5 exposure disrupts intestinal barrier integrity via microbial dysbiosis-triggered TLR2/5-MyD88-NLRP3 inflammasome activation - Zihan Ran; Jingcheng Yang; Liang Liu; Shaobo Wu; YanPeng An; Wanwan Hou; Tianyuan Cheng; Youyi Zhang; Yiqing Zhang; Yechao Huang; Qianyue Zhang; Jiaping Wan; et al. (Environmental Research, 2024)

Synthesis and fabrication of magnetically separable phosphate-modified magnetic chitosan composites for lead(II) selective removal from wastewater - Yaoyao Huang; Yuqi Peng; Guizhi Zhang; Zhengsijia Wu; Juan Li; Wei Ding; Hong Li; Yanyan An; Liang Ao; Yu Shen; Huaili Zheng (Environmental Research, 2024)

Fluorinated ionic liquid mediated nanostructure with enhanced conductivity and fluorine retention in Na3V2(PO4)2F3 cathode toward high-performance sodium-ion batteries - Yang Yan; Jun-Qing Xu; Jun-Ming Cao; Han-Wei Huang; Sen-Sen Xue; Guang-Lan Li; An-Min Liu; Cheng-Jie Li; Dongmei Dai; Bao Li; Xing-Long Wu (Chemical Engineering Journal, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

Different variations in PM2.5 sources and their specific health risks in different periods in a heavily polluted area of the Beijing-Tianjin-Hebei region of China - Jiwei Li; Lihong Ren; Yunfei Wu; Renjian Zhang; Xiaoyang Yang; Gang Li; Erhao Gao; Jiutao An; Yisheng Xu (Atmospheric Research, 2024)

Effects of combined biochar and maize straw applications on soil greenhouse gas emissions - Yongchun Zhou; Zili Zhao; Danyang Li; Liulin Wu; Zhimin Chen; Ning An; Jinrong Yang; Yapeng Wang (Applied Soil Ecology, 2024)

Expression analysis of pathogenesis-related protein genes revealed the key RrPRs involved in SA- and MeJA-mediated top-rot disease resistance in Rosa roxburghii fruit - Qi Wang; Mingui Li; Min Lu; Xiaomao Wu; Huaming An (Physiological and Molecular Plant Pathology, 2024)

Carbon footprint of fresh sea cucumbers in China: Comparison of three aquaculture technologies - Lin Yang; Dong An; Yuhu Cui; Xuexiu Jia; Dong Yang; Wensheng Li; Yanliang Wang; Longjie Wu (Journal of Cleaner Production, 2024)

Factors governing the dynamics of soil organic carbon and nitrogen in wetlands undergoing management changes in a semi-arid region - Yifan Li; Mingye Zhang; Yu An; Le Wang; Xuan Wang; Shouzheng Tong; Haitao Wu; Ming Jiang; Yue Guo; Li Jiang (Journal of Environmental Management, 2024)

Tin isotope heterogeneity and baseline of the upper continental crust - Jia-Xin She; Weiqiang Li; Edith Kubik; Frédéric Moynier; Xiang-Long Luo; Jun Mu; Shichao An; Chang-Zhi Wu; Zhongya Hu; Junfeng Ji (Geochimica et Cosmochimica Acta, 2024)

Understanding the extreme differentiation of granitic magmas through elemental geochemistry and Fe isotope signatures - Xiang-Long Luo; Chang-Zhi Wu; Jia-Xin She; Matthew J. Brzozowski; De-Hong Du; Shichao An; Weiqiang Li (Geochimica et Cosmochimica Acta, 2024)

Optimising microbial processes with nano-carbon/selenite materials: An eco-friendly approach for antibiotic resistance mitigation in broiler manure - Lizhi Li; Weikun Guan; Baohua Xiao; Qin He; Gangfu Chen; Jianzhong Wu; Zhigang Zhao; Feng You; Jinsheng Yang; Yue Xing; Lijun Zhou; Jinmeng Shi; et al. (Chemical Engineering Journal, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Activation AMPK in Hypothalamic Paraventricular Nucleus Improves Renovascular Hypertension Through ERK1/2-NF-κB Pathway - Li-Yan Fu; Yu Yang; Rui-Juan Li; Abdoulaye Issotina Zibrila; Hua Tian; Xiu-Yue Jia; Jin-An Qiao; Jin-Min Wu; Jie Qi; Xiao-Jing Yu; Yu-Ming Kang (Cardiovascular Toxicology, 2024)

Genetic analysis of Discogobio (Cypriniformes: Cyprinidae) in the Central Yunnan Basin: Effects of geological events and conservation perspectives - Xing‐Jin Che; Yuan‐Wei Zhang; An‐Li Wu; Li‐Mei Zhang; Xiao‐Fu Pan; Mo Wang; Jun‐Xing Yang; Xiao‐Ai Wang (Zoologica Scripta, 2024)
Geological events can have a major effect on the genetic structure and differentiation of fish populations. The relative importance of key geological events on the distribution and genetic structure of endemic fish of the genus Discogobio in the Yunnan–Guizhou Plateau has not yet been evaluated. Studies of the phylogeography of Discogobio fishes could provide insights into spatial and temporal changes in their population size, dispersal history, and extent of geographical isolation, and the data acquired in such studies can be used to aid their conservation. Here, we used single‐nucleotide polymorphisms (SNP) to characterize the phylogeography of Discogobio fishes. Our analysis supports the endemicity of Discogobio . However, Discogobio samples from different regions contained multiple ancestral components, including admixed and diversified genetic components. This might stem from polymorphism of the ancestors themselves or the infiltration of genes caused by hybridization between Discogobio species. We estimated that the most recent common ancestor (MRCA) of Discogobio fish in the Central Yunnan Basin was approximately 4.63–3.83 million years ago (Ma). We also inferred that the evolution of Discogobio in the Central Yunnan Basin was closely related to the expansion and contraction of the lake basin around 2.59–0.13 Ma. We proposed measures that could be implemented to conserve remaining populations and their corresponding habitats to prevent further declines and preserve the biodiversity of this unique genus.

Zinc oxide/graphene oxide nanocomposites specifically remediated Cd-contaminated soil via reduction of bioavailability and ecotoxicity of Cd - Yang Li; Lei Cheng; Baolin Yang; Yuting Ding; Yanan Zhao; Yuanyuan Wu; Yaguang Nie; Yun Liu; An Xu (Science of The Total Environment, 2024)

Characterization, hazard identification, and risk assessment of volatile organic compounds in Poly(butylene adipate-co-terephthalate)-based food contact articles - Hanke Li; Hongjian Miao; Lichang Chen; Qi-Zhi Su; Zhenwei Liu; Canghao Xie; Jinxin Liang; Siliang Wu; An-Qi Cui; Can Xu; Ben Dong; Dan Li; et al. (Food and Chemical Toxicology, 2024)

Photoluminescence-Tunable organic phosphine cuprous halides clusters for X-ray scintillators and white light emitting diodes - Jun’an Lai; Chen Li; Zixian Wang; Linfeng Guo; Yijia Wang; Kang An; Sijun Cao; Daofu Wu; Zhengzheng Liu; Zhiping Hu; Yuxin Leng; Juan Du; et al. (Chemical Engineering Journal, 2024)

Hybrid cell membranes camouflaged copper-loaded nano-prodrug for tumor angiogenesis inhibition and cell cuproptosis - Xian Qin; Li Zhu; Xuan An; Cheng Zhang; Jiawei Li; Fei Yan; Wenjin Zhang; Kai Qu; Kun Zhang; Wei Wu; Guicheng Wu (Chemical Engineering Journal, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

A self-assembled 3D nanoflowers based nano-ELISA platform for the sensitive detection of pyridaben - He Chen; Li An; Meng Li; Hao Liu; Zhong Jin; Huan Ma; Jingwei Ma; Juan Zhou; Ran Duan; Di Zhang; Xiu Cao; Tieliang Wang; et al. (Food Chemistry, 2024)

SIRT6 positively regulates antiviral response in a bony fish, the Chinese perch Siniperca chuatsi - Xiang Yang Wu; Zhi Wei Zhang; Shan Nan Chen; An Ning Pang; Xue Yun Peng; Nan Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2024)

Porous polyvinyl alcohol/polyacrylamide hydrogels loaded with HTO lithium-ion sieves for highly rapid and efficient Li+ extraction - Xunshuang Zhang; Junxiang Wu; Yu He; Chenhao Zhao; Minfang An; Liangbin Li (Desalination, 2024)

Correction: Areca Thirteen Pill Improves Depression in Rat by Modulation of the Chemokine/Chemokine Receptor Axis - Jing-jing Bai; Min Ao; An Xing; Li-jun Yu; Hai-ying Tong; Wu-ye Bao; Yu Wang (Molecular Neurobiology, 2024)

Areca Thirteen Pill Improves Depression in Rat by Modulation of the Chemokine/Chemokine Receptor Axis - Jing-jing Bai; Min Ao; An Xing; Li-jun Yu; Hai-ying Tong; Wu-ye Bao; Yu Wang (Molecular Neurobiology, 2024)

Prediction of significant wave height using a VMD-LSTM-rolling model in the South Sea of China - Tong Ding; De’an Wu; Liangshuai Shen; Qiang Liu; Xiaogang Zhang; Yuming Li (Frontiers in Marine Science, 2024)
Accurate prediction of significant wave height is crucial for ocean engineering. Traditional time series prediction models fail to achieve satisfactory results due to the non-stationarity of significant wave height. Decomposition algorithms are adopted to address the problem of non-stationarity, but the traditional direct decomposition method exists information leakage. In this study, a hybrid VMD-LSTM-rolling model is proposed for non-stationary wave height prediction. In this model, time series are generated by a rolling method, after which each time series is decomposed, trained and predicted, then the predictions of each time series are combined to generate the final prediction of significant wave height. The performance of the LSTM model, the VMD-LSTM-direct model and the VMD-LSTM-rolling model are compared in terms of multi-step prediction. It is found that the error of the VMD-LSTM-direct model and the VMD-LSTM-rolling model is lower than that of the LSTM model. Due to the decomposition of the testing set, the VMD-LSTM-direct model has a slightly higher accuracy than the VMD-LSTM-rolling model. However, given the issue of information leakage, the accuracy of the VMD-LSTM-direct model is considered false. Thus, it has been proved that the VMD-LSTM-rolling model exhibits superiority in predicting significant wave height and can be applied in practice.

Fault diagnosis of wind turbine blade icing based on feature engineering and the PSO-ConvLSTM-transformer - Jicai Guo; Xiaowen Song; Shufeng Tang; Yanfeng Zhang; Jianxin Wu; Yuan Li; Yan Jia; Chang Cai; Qing'an Li (Ocean Engineering, 2024)

Multi-perspective interpretation for one-dimensional conventional neural network model to identify iron-bearing waste material - Chenglin Yan; Shu Liu; Zhixiu Zhu; Hong Min; Qingjian Zhang; Wenya Zhao; Piao Su; Yarui An; Chen Li; Xiaohong Wu (Journal of Environmental Chemical Engineering, 2024)

Silkworm pupae globulin promotes Cordyceps militaris fermentation: Regulation of metabolic pathways enhances cordycepin synthesis and extends the synthesis phase - Yi-Tong Li; Hao-Tian Yao; Ze-Lai Huang; Lu-Chan Gong; Richard A. Herman; Fu-An Wu; Jun Wang (Food Bioscience, 2024)

Effect of different valence metal cations on the gel characteristics and microstructure of Inca peanut albumin gels - Honglang Liu; Yongqing Wu; Yanxin Li; Xin-an Xie; Pan Li; Bing Du; Lu Li (Food Hydrocolloids, 2024)

Anti-fouling coating with ROS-Triggered On-Demand regulation of inflammation to favor tissue healing on vascular devices - Hui Yan; Lietao Wang; Haoshuang Wu; Yongqi An; Yumei Qin; Zhen Xiang; Huining Wan; Yanfei Tan; Li Yang; Fanjun Zhang; Qing Jiang; Rifang Luo; et al. (Chemical Engineering Journal, 2024)

Identification of candidate genes for Fusarium head blight resistance from QTLs using RIL population in wheat - Mingxia Zhang; Peng Jiang; Qun Wu; Xu Han; Junxia Man; Junsheng Sun; Jinlong Liang; Jingchuan Chen; Qi Zhao; Ying Guo; Yanrong An; Haiyan Jia; et al. (Plant Molecular Biology, 2024)

Characteristics and whole-genome analysis of a novel Pseudomonas syringae pv. tomato bacteriophage D6 isolated from a karst cave - Qingshan Wu; Ni An; Zheng Fang; Shixia Li; Lan Xiang; Qiuping Liu; Leitao Tan; Qingbei Weng (Virus Genes, 2024)
Pseudomonas syringae is a gram-negative plant pathogen that infects plants such as tomato and poses a threat to global crop production. In this study, a novel lytic phage infecting P. syringae pv. tomato DC3000, named phage D6, was isolated and characterized from sediments in a karst cave. The latent period of phage D6 was found to be 60 min, with a burst size of 16 plaque-forming units per cell. Phage D6 was stable at temperatures between 4 and 40 °C but lost infectivity when heated to 70 °C. Its infectivity was unaffected at pH 6–10 but became inactivated at pH ≤ 5 or ≥ 12. The genome of phage D6 is a linear double-stranded DNA of 307,402 bp with a G + C content of 48.43%. There is a codon preference between phage D6 and its host, and the translation of phage D6 gene may not be entirely dependent on the tRNA library provided by the host. A total of 410 open reading frames (ORFs) and 14 tRNAs were predicted in its genome, with 92 ORFs encoding proteins with predicted functions. Phage D6 showed low genomic similarity to known phage genomes in the GenBank and Viral sequence databases. Genomic and phylogenetic analyses revealed that phage D6 is a novel phage. The tomato plants were first injected with phage D6, and subsequently with Pst DC3000, using the foliar spraying and root drenching inoculum approach. Results obtained after 14 days indicated that phage D6 inoculation decreased P. syringae- induced symptoms in tomato leaves and inhibited the pathogen’s growth in the leaves. The amount of Pst DC3000 was reduced by 150- and 263-fold, respectively. In conclusion, the lytic phage D6 identified in this study belongs to a novel phage within the Caudoviricetes class and has potential for use in biological control of plant diseases.

Improving urban CO2 spatial distribution modelling using multi-source data - Erchang Sun; Xianhua Wang; Hanhan Ye; Shichao Wu; Hailiang Shi; Dacheng Li; Yuan An; Chao Li (Urban Climate, 2024)

Early bearing fault diagnosis for imbalanced data in offshore wind turbine using improved deep learning based on scaled minimum unscented kalman filter - Hai-Hong Tang; Kun Zhang; Bing Wang; Xiao-jia Zu; You-Yi Li; Wu-Wei Feng; Xue Jiang; Peng Chen; Qing-An Li (Ocean Engineering, 2024)

Effects of multi-year droughts on the precipitation-runoff relationship: An integrated analysis of meteorological, hydrological, and compound droughts - Jiefeng Wu; Pengyu An; Chenxi Zhao; Ziqi Wei; Tian Lan; Xuemei Li; Guoqing Wang (Journal of Hydrology, 2024)

Simulation of dynamic pulsing fracking in poroelastic media by a hydro-damage-mechanical coupled cohesive phase field model - Hui Li; Zhenjun Yang; Fengchen An; Jianying Wu (Engineering Geology, 2024)

Utilization of unrejected ammonium for fouling prevention in a forward osmosis process tested with real primary wastewater from Hong Kong - Paula Jungwon Choi; Xinning Zhang; Noman Khalid Khanzada; Di Wu; Ling Li; Am Jang; Alicia Kyoungjin An (Desalination, 2024)

Macrophage membrane-modified reactive oxygen species-responsive prodrug self-assembled nanoparticles for the targeted treatment of traumatic spinal cord injury - Jinyu An; Zhanshan Gao; Yingqiao Li; Nan Xia; Xiaobang Liu; Huicong Feng; Chao Wu; Xifan Mei; He Tian (Chemical Engineering Journal, 2024)

Gelsenicine disrupted the intestinal barrier of Caenorhabditis elegans - Zekai Wu; Jian Zhang; Yajiao Wu; Mengting Chen; Hong Hu; Xinyue Gao; Chutao Li; Maodong Li; Youbo Zhang; Xiaohuang Lin; Qiaomei Yang; Li Chen; et al. (Chemico-Biological Interactions, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

A new diterpenoid from the leaves and twigs of Croton lachnocarpus Benth - Xiao-Qing Zhan; Qian Wu; Mei-Jie Wang; Li Liu; Wen-Bo Cui; Feng-Li An; Feng-Ming Qi; Dong-Qing Fei; Zhan-Xin Zhang (Natural Product Research, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Atomically dispersed Fe-N-C catalyst with densely exposed Fe-N4 active sites for enhanced oxygen reduction reaction - Xiangyu Lu; Yaqiang Li; Peixia Yang; Yongbiao Wan; Dan Wang; Hao Xu; Lilai Liu; Lihui Xiao; Ruopeng Li; Guangzhao Wang; Jinqiu Zhang; Maozhong An; et al. (Chemical Engineering Journal, 2024)

Anisotropic materials based on carbohydrate polymers: A review of fabrication strategies, properties, and applications - Qi An; Jingnan Ren; Xiao Jia; Shasha Qu; Nawei Zhang; Xiao Li; Gang Fan; Siyi Pan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2024)

Dynamics of copper, cadmium, chromium, and lead storage in a subtropical forest headwater stream - Yutong Zhang; Qiqi Li; Yan Peng; Chunping Huang; Zemin Zhao; Chaoxiang Yuan; Nannan An; Fuzhong Wu; Xiangyin Ni; Kai Yue (Aquatic Sciences, 2024)

A hybrid CEEMDAN-VMD-TimesNet model for significant wave height prediction in the South Sea of China - Tong Ding; De’an Wu; Yuming Li; Liangshuai Shen; Xiaogang Zhang (Frontiers in Marine Science, 2024)
Accurate prediction of significant wave height is of great reference value for wave energy generation. However, due to the non-linearity and non-stationarity of significant wave height, traditional algorithms face difficulties in achieving satisfactory prediction results. In this study, a hybrid CEEMDAN-VMD-TimesNet model is proposed for non-stationary significant wave height prediction. Based on the significant wave height in the South Sea of China, the performance of the SVM model, the GRU model, the LSTM model, the TimesNet model, the CEEMDAN-TimesNet model and the CEEMDAN-VMD-TimesNet model are compared in terms of multi-step prediction. It is found that the prediction accuracy of the TimesNet model is higher than that of the SVM model, the GRU model and the LSTM model. The non-stationarity of significant wave height is reduced by CEEMDAN decomposition. Thus, the CEEMDAN-TimesNet model performs better than the TimesNet model in predicting significant wave height. The prediction accuracy of the CEEMDAN-VMD-TimesNet model is further improved by employing VMD for the secondary decomposition of components with high and moderate complexity. Additionally, the CEEMDAN-VMD-TimesNet model can accurately predict trends and extreme values of significant wave height with minimal phase shifts even during typhoon periods. The results demonstrate that the CEEMDAN-VMD-TimesNet model exhibits superiority in predicting significant wave height.

Suppression of neutrophil extracellular traps is responsible for the amelioration of chemotherapeutic intestinal injury by the natural compound PEITC - Mei Bai; Shuaifei Li; Cui Zhang; Ning An; Jie Wang; Jia Qin; Rumeng Jia; Wentao Liu; Jingcai Cheng; Xuefeng Wu; Qiang Xu (Toxicology and Applied Pharmacology, 2024)

Utilizing different types of biomass materials to modify steel slag for the preparation of composite materials used in the adsorption and solidification of Pb in solutions and soil - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Fanmin Zhu; Zhanbin Huang (Science of The Total Environment, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

SAR interferometry on full scatterers: Mapping ground deformation with ultra-high density from space - Hong'an Wu; Yonghong Zhang; Yonghui Kang; Jujie Wei; Zhong Lu; Wei Yan; Haigang Wang; Zhenhui Liu; Xiaowen Lv; Maotong Zhou; Kui Li; Ying Liu; et al. (Remote Sensing of Environment, 2024)

A combined and sustainable approach and a novel mechanism for recovering Bi, Au and Ag from high-chloride leachate of waste printed circuit board smelting ash - Gongqi Liu; Yufeng Wu; Bin Li; Haoran Yuan; Jing Gu; De’an Pan (Journal of Hazardous Materials, 2024)

Synergistic evolution of water-energy-food system resilience and efficiency in urban agglomerations - Hui An; Xiangyang Li; Jin Huang; Hailin Wu (Journal of Environmental Management, 2024)

Association of short-term PM2.5 exposure with airway innate immune response, microbiota and metabolism alterations in human airways - Shuaiqi Zhao; Huijun Li; Fuyun Yang; Yishu Yang; Yuling Zeng; Zhen An; Juan Li; Hui Wu; Jie Song; Weidong Wu (Environmental Pollution, 2024)

Molecular self-assembled cellulose enabling durable, scalable, high-power osmotic energy harvesting - Jianping Shi; Xuhui Sun; Yu Zhang; Shengyue Niu; Zequn Wang; Zhuotong Wu; Meng An; Lihui Chen; Jianguo Li (Carbohydrate Polymers, 2024)

Effects of sewage sludge application methods on the transport of heavy metals with runoff and their mechanisms - Yuantong Yang; Weixun Feng; Li'an Bao; Lihua Xian; Jie Lu; Daoming Wu; Douglass F. Jacobs; Shucai Zeng (Science of The Total Environment, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Chiral D-peptide supramolecular hydrogel for minimizing postoperative pancreatic fistula by devitalizing pancreatic enzymes - Xiao Li; Yang Wang; Juzheng Yuan; Jiaze An; Siqi Yan; Weikang Wu; Wangxiao He; Jin Yan; Kaishan Tao (Chemical Engineering Journal, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Kinetic modeling of cell growth and value-added products accumulation of Thraustochytrium striatum - Rui Xiao; Zhaohui An; Xiang Li; Zhi-Wu Wang; Yi Zheng (Biomass and Bioenergy, 2024)

Potential impacts of coal mining activities on nitrate sources and transport in a karst river basin in southwest China - Li An; Qingguang Li; Pan Wu; Weiqi Lu; Xuexian Li; Chipeng Zhang; Ruixue Zhang (Environmental Science and Pollution Research, 2024)

Data Quality Control Method of a New Drifting Observation Technology Named Drifting Air-Sea Interface Buoy - Shuo Li; Bin Wang; Zeng’an Deng; Baoqin Wu; Xiande Zhu; Zhaohui Chen (Journal of Ocean University of China, 2024)

Stability of the Stratification of Water Bodies in the North Passage of the Yangtze River Estuary Based on the EFDC Model - De’an Wu; Xin Li; Yigang Wang (Journal of Ocean University of China, 2024)

Fluctuating redox conditions accelerate the electron storage and transfer in magnetite and production of dark hydroxyl radicals - Dan Li; Jieyi Sun; Yibo Fu; Wentao Hong; Heli Wang; Qian Yang; Junhong Wu; Sen Yang; Jianhui Xu; Yunfei Zhang; Yirong Deng; Yin Zhong; et al. (Water Research, 2024)

Piriformospora indica colonization enhances remediation of cadmium and chromium co-contaminated soils by king grass through plant growth promotion and rhizosphere microecological regulation - Kailu Zhang; Haixiang Zhang; Can Xie; Zhiqiang Zhu; Li Lin; Qianli An; Xin Zhang; Weidong Wu; Dong Li (Journal of Hazardous Materials, 2024)

Structure evolution of porous alumina during aging process and its support effect on PtSn/Al2O3 catalyzed propane dehydrogenation - Haowei Wang; Wen-Cui Li; Xinqian Gao; Shuzhen Zhou; Yu Zhang; Fan Wu; An-Hui Lu (Chemical Engineering Journal, 2024)

Mechanically stable superhydrophobic coating of crosslinked polymer composite with self-healing ability - Xiao-Jing Guo; Meng-Chen Huang; Chao-Hua Xue; Hui-Di Wang; Zhong-Xue Bai; Yong-Gang Wu; Chao-Qun Ma; Zhong-Yang Shao; Zi-Hao Jiang; Li Wan; A-Jun Chang; Jing Li; et al. (Chemical Engineering Journal, 2024)

Integrated ultra-low PtIr catalyst coated membrane toward efficient proton exchange membrane water electrolyzers - Jiaqi Qin; Yang Lv; Guangqi Han; Huiyuan Liu; Yongpeng Li; Hongyan Zhang; Xiaoyu Zhou; Keran Xing; Tiantian Li; Chongyun Sun; Chunxiao Wang; Qiang Zhou; et al. (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Five-impulse low-energy earth-moon transfer using manifolds - Shiyu An; Ming Liu; Huayi Li; Fan Wu (Advances in Space Research, 2024)

Declining coupling between vegetation and drought over the past three decades - Delong Li; Li An; Shuai Zhong; Lei Shen; Shuyao Wu (Global Change Biology, 2024)
Droughts have been implicated as the main driver behind recent vegetation die‐off and are projected to drive greater mortality under future climate change. Understanding the coupling relationship between vegetation and drought has been of great global interest. Currently, the coupling relationship between vegetation and drought is mainly evaluated by correlation coefficients or regression slopes. However, the optimal drought timescale of vegetation response to drought, as a key indicator reflecting vegetation sensitivity to drought, has largely been ignored. Here, we apply the optimal drought timescale identification method to examine the change in coupling between vegetation and drought over the past three decades (1982–2015) with long‐term satellite‐derived Normalized Difference Vegetation Index and Standardized Precipitation‐Evapotranspiration Index data. We find substantial increasing response of vegetation to drought timescales globally, and the correlation coefficient between vegetation and drought under optimal drought timescale overall declines between 1982 and 2015. This decrease in vegetation–drought coupling is mainly observed in regions with water deficit, although its initial correlation is relatively high. However, vegetation in water‐surplus regions, with low coupling in earlier stages, is prone to show an increasing trend. The observed changes may be driven by the increasing trend of atmospheric CO 2 . Our findings highlight more pressing drought risk in water‐surplus regions than in water‐deficit regions, which advances our understanding of the long‐term vegetation–drought relationship and provides essential insights for mapping future vegetation sensitivity to drought under changing climate conditions.

Ce doped V-W/Ti as selective catalytic reduction catalysts for cement kiln flue gas denitration - Yu Qin; Wentao Cai; Zeyan Li; Genan Li; Pengfei Liu; Baodeng An; Kan Wu; Jun Gu (Environmental Science and Pollution Research, 2023)

Short-term ozone exposure and serum neural damage biomarkers in healthy elderly adults: Evidence from a panel study - Rongrong Qu; Beibei Sun; Jing Jiang; Zhen An; Juan Li; Hui Wu; Weidong Wu; Jie Song (Science of The Total Environment, 2023)

High temperature exacerbates ozone-induced airway inflammation: Implication of airway microbiota and metabolites - Fei Xu; Qiong Wu; Yishu Yang; Ling Zhang; Zhen Yan; Huijun Li; Juan Li; Zhen An; Hui Wu; Jie Song; Weidong Wu (Science of The Total Environment, 2023)

Erythromycin fermentation residue exposure induces a short-term wave of antibiotic resistance in a soil-lettuce system - Jieya Zhou; Hao Wu; Zongru Wu; Lihu Shi; Yunpeng Shen; Shulei Tian; Li-an Hou (Science of The Total Environment, 2023)

Crushing characteristics and performance evaluation of iron ore in a cone crusher: A numerical study - Chuanning Jiang; Dazhao Gou; Chao Li; Guanyin Wu; Xizhong An; Ju Wang; Pengyue Guo (Minerals Engineering, 2023)

Acid-modified red mud biochar for the degradation of tetracycline: Synergistic effect of adsorption and nonradical activation - Bohan Xu; Qiang An; Shuman Deng; Zheng Li; Zihao Yang; Haoyu Wu; Zhihong Ye (Journal of Environmental Management, 2023)

Effects of vegetation restoration on the concentrations of multiple metal elements in post-mining soils - Qiqi Li; Chaoxiang Yuan; Qiqian Wu; Yan Peng; Zemin Zhao; Yiqing Wang; Nannan An; Xiangyin Ni; Fuzhong Wu; Kai Yue (Journal of Environmental Management, 2023)

Simultaneous determination of spiropidion and its five major metabolites in sweet orange fruit and various processing by-products using ultra-high performance liquid chromatography-tandem mass spectrometry - Zhi Wu; Yuan Ma; Huan Xiong; Wenjin An; Yaohai Zhang; Qiyang Zhao; Jing Li (Food Research International, 2023)

Effectiveness of potato late blight (Phytophthora infestans) forecast by meteorological estimation in mountainous terrain based on CARAH rules - Qiang Wu; Yuan-yan Yang; Okbagaber Andom; Yan-li Li; Zi-zi Luo; An-hong Guo (Fungal Biology, 2023)

Microplastics released from disposable medical devices and their toxic responses in Caenorhabditis elegans. - Tong Zhou; Jiajie Wu; Xi Hu; Zhenxiao Cao; Baolin Yang; Yang Li; Yanan Zhao; Yuting Ding; Yun Liu; An Xu (Environmental Research, 2023)

New dechlorination products and mechanisms of tris(2-chloroethyl) phosphate by an anaerobic enrichment culture from a vehicle dismantling site - Sen Yang; Junhong Wu; Heli Wang; Qian Yang; Huanheng Zhang; Lihua Yang; Dan Li; Yirong Deng; Yin Zhong; Ping'an Peng (Environmental Pollution, 2023)

Characterization of polycyclic aromatic hydrocarbons (PAHs) in atmospheric particles (PM2.5) in the North China Plain using positive-ion atmospheric pressure photoionization (APPI) coupled with fourier transform ion cyclotron resonance mass spectrometry (FT-ICR MS) - Hao Sun; Li Wang; Xinyuan Kang; Zilan Wu; Haoran Yu; Ren'an Wu; Lan Yao; Jianmin Chen (Atmospheric Environment, 2023)

Socioeconomic status, lifestyle and risk of incident dementia: a prospective cohort study of 276730 participants - Ya-Nan Ou; Yan-Bo Zhang; Yu-Zhu Li; Shu-Yi Huang; Wei Zhang; Yue-Ting Deng; Bang-Sheng Wu; Lan Tan; Qiang Dong; An Pan; Ren-Jie Chen; Jian-Feng Feng; et al. (GeroScience, 2023)

Study on controllable preparation of high performance andradite based glass-ceramics by harmful iron-rich waste slag - Xiaomin Liu; Yufeng Wu; De'an Pan; Bin Li; Wei Wang (Science of The Total Environment, 2023)

The introduction of nitrogen from coal into the surface watershed nitrogen cycle due to coal mining activity - Qingguang Li; Li An; Pan Wu; Shilu Wang; Shangyi Gu; Yongqiang Yuan; Yong Fu (Science of The Total Environment, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Prognostic value of left ventricular systolic function on moderate aortic stenosis: the China-VHD study - Xianbao Liu; Qifeng Zhu; Qiong Liu; Haiyan Xu; Hanyi Dai; Yaoyao Zhou; Jun Chen; Stella Ng; Ye Lu; Yanyan Zhao; Zhe Li; Yongjian Wu; et al. (Science Bulletin, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

Zebrafish nos2a benefits bacterial proliferation via suppressing ROS and inducing NO production to impair the expressions of inflammatory cytokines and antibacterial genes - Si Yao Zheng; Xinbin Shao; Zhitao Qi; Maocang Yan; Min Hui Tao; Xiao Man Wu; Lining Zhang; Jianzhong Ma; An Li; Ming Xian Chang (Fish & Shellfish Immunology, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Tuning 3D refractive indices via constrained uniaxial stretch in cellulose triacetate films plasticized with triethyl citrate - Xueqing Han; Xiaoyu Min; Tong Wu; Minfang An; Lingpu Meng; Liangbin Li; Kunpeng Cui (Carbohydrate Polymers, 2023)

Ultrafine particles in urban settings: A combined study of volatility and effective density revealed by VT-DMA-APM - Che-An Wu; Yu-Ting Chen; Li-Hao Young; Po-Kai Chang; Li-Ti Chou; Albert Y. Chen; Ta-Chih Hsiao (Atmospheric Environment, 2023)

Hybrid machine learning model for hourly ozone concentrations prediction and exposure risk assessment - Wu Lingxia; Zhang Qijie; Li Jie; An Junlin (Atmospheric Pollution Research, 2023)

An MLS-based high-accuracy measurement and automatic analysis method for roadway deformation - Chao Wu; Yuanhui Li; Long An; Erhu Dong; Lin Han (Tunnelling and Underground Space Technology, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

Sodium butyrate alleviates deoxynivalenol-induced porcine intestinal barrier disruption by promoting mitochondrial homeostasis via PCK2 signaling - Dongfang Xue; Yating Cheng; Tiantian Pang; Yunyi Kuai; Yu An; Kuntan Wu; Yuqing Li; Mengyu Lai; Bihan Wang; Shuai Wang (Journal of Hazardous Materials, 2023)

Experimental and mechanistic study on the removal of lead from solution by sulfuric acid modified steel slag adsorbent - An Wang; Meiling Wu; Zhongyuan Li; Yuqiang Zhou; Zhanbin Huang (Journal of Environmental Chemical Engineering, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Undescribed steroidal alkaloids from the bulbs of Fritillaria sinica - Jia-yuan Li; Shi-fei Wu; Ya-ling An; Chang-liang Yao; Shuai Yao; Yong Huang; Wen-long Wei; Jian-qing Zhang; Qi-rui Bi; Hua Qu; De-an Guo (Phytochemistry, 2023)

Host trehalose metabolism disruption by validamycin A results in reduced fitness of parasitoid offspring - Yan Song; Fengming Gu; Yijiangcheng Li; Weihong Zhou; Fu-an Wu; Jun Wang; Sheng Sheng (Pesticide Biochemistry and Physiology, 2023)

Novel Ag-bridged dual Z-scheme g-C3N4/BiOI/AgI plasmonic heterojunction: Exceptional photocatalytic activity towards tetracycline and the mechanism insight - Wenxia Wang; Zhen Li; Kailin Wu; Guodong Dai; Qingping Chen; Lihua Zhou; Junxia Zheng; Liang Ma; Guiying Li; Wanjun Wang; Taicheng An (Journal of Environmental Sciences, 2023)

Knockdown of Long Noncoding RNA CCAT2 Suppresses Malignant Phenotype in Human Laryngeal Squamous Cell Carcinoma - M. Li; J. An; H. Ren; J. Gui; H. Wang; S. Wu; R. Wu; H. Xiao; L. Wang (Bulletin of Experimental Biology and Medicine, 2023)

ZmMS1/ZmLBD30-orchestrated transcriptional regulatory networks precisely control pollen exine development - Quancan Hou; Xueli An; Biao Ma; Suowei Wu; Xun Wei; Tingwei Yan; Yan Zhou; Taotao Zhu; Ke Xie; Danfeng Zhang; Ziwen Li; Lina Zhao; et al. (Molecular Plant, 2023)

Internal exposure risk based on urinary metabolites of PAHs of occupation and non-occupation populations around a non-ferrous metal smelting plant - Bizhi Wu; Meiqing Lin; Hailing Li; Yingjun Wu; Mengdie Qi; Jian Tang; Shengtao Ma; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2023)

Preparation of carbon foam from depolymerization-reforming lignin for capacitive deionization - Chun-Ping Li; Ya-Qi Wu; Jia-Jia An; Li-Xin Gao; Da-Quan Zhang; Jin Li; Zhong-Xun An (Desalination, 2023)

Highly fractionated Hg isotope evidence for dynamic euxinia in shallow waters of the Mesoproterozoic ocean - Yaowen Wu; Hui Tian; Runsheng Yin; Di Chen; Stephen E. Grasby; Jun Shen; Tengfei Li; Sui Ji; Ping'an Peng (Earth and Planetary Science Letters, 2023)

Spawning characteristics of blue sprat (Spratelloides gracilis) in the waters of Penghu, central Taiwan Strait - Li Chi Cheng; Yang Chi Lan; Kuo Wei Lan; Jinn Shing Weng; Yu Kai Chen; Sheng Tai Hsiao; Yi Sui Wu; Jia Shin He; Hsing Han Huang; Yu Cih Huang; Hung An Cheng (Frontiers in Marine Science, 2023)
Blue sprat ( Spratelloides gracilis ) is an economically valuable species that inhabits the central Taiwan Strait. However, despite the implementation of a local management scheme involving a closed season between 1 May and 1 June, the annual catch has rapidly decreased over the decades. Thus, the efficacy of the implemented regulations must be investigated. This study sought to clarify the reproductive biology, spawning ground, and behavior of this species in the waters of Penghu. In total, 6,549 specimens were collected between March 2021 and September 2022. Considering gonadosomatic index, group maturity, and oocyte diameter, we found that the spawning season (March–September) peaked in April; new cohorts were distinctly recruited after the spawning peak. The distribution of the spawning ground (latitude, 23°41′N to 23°43′N; longitude, 119°32′E to 119°39′E) was determined by considering the fishing area of mature females and DNA analysis of adhered eggs. We further noted shoals of fish darting in the bottom water without clear schooling movement, females’ abdomen frequently contacting substrata for eggs able to attach on during oviposition, and males releasing sperms making water milky white; these indicate that S. gracilis exhibits promiscuous spawning behavior. Our findings may facilitate the management and conservation of S. gracilis in this region.

Highly oxygenated germacrane-type sesquiterpenoids from the whole plant of Salvia cavaleriei H.Lév. and their biological activities - Xiao-Han Chen; Xu Liu; Wen-Bo Cui; Feng-Li An; Li Liu; Qian Wu; Jian-Ning Yu; Jian-Ye Dai; Zhan-Xin Zhang; Dong-Qing Fei (Phytochemistry, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Degradation performance and bioinformatic analysis of graphite electrode electrolysis cells for erythromycin fermentation residue - Jieya Zhou; Zongru Wu; Shuai Wang; Hao Wu; Lihu Shi; Shulei Tian; Li-an Hou (Journal of Cleaner Production, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Four new phenolic compounds from the fruits of Alpinia galanga - Pei Liu; Sheng-Li Wu; Tian Wang; Xue-Mei Zhang; Chang-An Geng (Phytochemistry Letters, 2023)

Photoelectrocatalytic selective removal of group-targeting thiol-containing heterocyclic pollutants - Baoling Niu; Zhiming Wang; Jianwei Wu; Junzhuo Cai; Ziwen An; Jie Sun; Yanbo Li; Shuyu Huang; Ning Lu; Qihao Xie; Guohua Zhao (Journal of Hazardous Materials, 2023)

Structural characteristics and gel properties of pectin from citrus physiological premature fruit drop - Tingting Qi; Jingnan Ren; Xiao Li; Qi An; Nawei Zhang; Xiao Jia; Siyi Pan; Gang Fan; Zhifeng Zhang; Kangning Wu (Carbohydrate Polymers, 2023)

Temporal decline of genetic differentiation among populations of western flower thrips across an invaded range - Li-Na Sun; Li-Jun Cao; Jin-Cui Chen; Li-Jun Ma; Gui-Fen Zhang; San-An Wu; Ary Anthony Hoffmann; Shu-Jun Wei (Biological Invasions, 2023)

Applications of vacancy defect engineering in persulfate activation: Performance and internal mechanism - Ting Zhang; Shuang Wu; Ning Li; Guanyi Chen; Li’an Hou (Journal of Hazardous Materials, 2023)

A novel reutilization of ash from biomass gasification process: Feasibility and products improvement analysis - Qianqian Guo; Beibei Yan; Yanjun Hu; Xiang Guo; Wenzhu Wu; Zhanjun Cheng; Guanyi Chen; Li'an Hou (Fuel, 2023)

Analysis of the Interdecadal and Interannual Variability of Autumn Extreme Rainfall in Taiwan Using a Deep-Learning-Based Weather Typing Approach - Li-Huan Hsu; Yi-chao Wu; Chou-Chun Chiang; Jung-Lien Chu; Yi-Chiang Yu; An-Hsiang Wang; Ben Jong-Dao Jou (Asia-Pacific Journal of Atmospheric Sciences, 2023)

Occurrence of microplastics in commercially sold bottled water - Huan LI; Long ZHU; Mindong MA; Haiwen WU; Lihui AN; Zhanhong YANG (Science of The Total Environment, 2023)

RETRACTED: Treatment to surfactant containing wastewater with membrane distillation membrane with novel sandwich structure - Hanyu Guo; Haifu Gao; An Yan; Xiaolong Lu; Chunrui Wu; Li Gao; Jianhua Zhang (Science of The Total Environment, 2023)

Molybdenum isotope evidence from restricted-basin mudstones for an intermediate extent of oxygenation in the late Ediacaran ocean - Zhaozhao Tan; Jinxiang Wu; Wanglu Jia; Jie Li; Brian Kendall; Jianzhong Song; Ping’an Peng (Chemical Geology, 2023)

Self-assembled DNA nanoparticles enable cascade circuits for mRNA detection and imaging in living cells - Zhe Dong; Debo Gao; Yuancheng Li; Kang An; Jing Ni; Ling Meng; Han Wu (Analytica Chimica Acta, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Fish damage due to tubular turbine: Experiments and CFD simulations - Chunxia Yang; Qian Li; Ding'e Xu; Jiawei Wu; Yuan Zheng; Yuquan Zhang; An Yu (Ocean Engineering, 2023)

Sustainable on-farm strategy for the disposal of antibiotic fermentation residue: Co-benefits for resource recovery and resistance mitigation - Jieya Zhou; Hao Wu; Lihu Shi; Xuming Wang; Yunpeng Shen; Shulei Tian; Li-an Hou (Journal of Hazardous Materials, 2023)

Sonocatalytic degradation of tetracycline by BiOBr/FeWO4 nanomaterials and enhancement of sonocatalytic effect - Liang Xu; Xue-Qian Wu; Chun-Yu Li; Ni-Ping Liu; Hui-Li An; Wan-Ting Ju; Wen Lu; Bin Liu; Xiao-Fang Wang; Yang Wang; Xin Wang (Journal of Cleaner Production, 2023)

A particle-scale investigation of mechanical behavior of cemented hydrate-bearing sediment using Discrete Element Method - Yanghui Li; Jiayu Li; Zeshao You; Peng Wu; Yong Qu; An Zhang; Xiang Sun; Yongchen Song (Geomechanics for Energy and the Environment, 2023)

Efficient acquisition of high-purity cyanidin-3-O-glucoside from mulberry fruits: An integrated process of ATPS whole-cell transformation and semi-preparative HPLC purification - Yi-Tong Li; Ting Huang; Jin-Zheng Wang; Cheng-Hai Yan; Lu-Chan Gong; Fu-An Wu; Jun Wang (Food Chemistry, 2023)

Two pathways drive enhanced nitrogen acquisition via a complementarity effect in long-term intercropping - Yi Xing; Rui-Peng Yu; Ran An; Ning Yang; Jin-Pu Wu; Huai-Ying Ma; Jiu-Dong Zhang; Xing-Guo Bao; Hans Lambers; Long Li (Field Crops Research, 2023)

Estimation of mechanical and hydraulic parameters of bentonite-soil mixtures in oedometer condition with index properties - An Li; Wen-Bo Chen; Ze-Jian Chen; Pei-Chen Wu; Jian-Hua Yin; Chao Zhou (Bulletin of Engineering Geology and the Environment, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Evaluation of Fe3O4-MnO2@RGO magnetic nanocomposite as an effective persulfate activator and metal adsorbent in aqueous solution - Mang Lu; Xue-jiao Wu; Chu-xing Wan; Qiu-ping Gong; Jia-xin Li; Shuang-shuang Liao; Yu-an Wang; Shu-hao Yuan (Environmental Science and Pollution Research, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Six first-line tyrosine kinase inhibitors reveal novel inhibition potential for the EGFR S768I mutation - Ying Wang; Qian Liu; Chunhong Chu; Lanxin Li; Zhenxing Wang; Qiyu Liu; Guangyao Wu; Xiangkai Wei; Lei An; Jiguang Ma (Toxicology and Applied Pharmacology, 2023)

Response of sediment microbial communities to different levels of PAC contamination and exposure time - Xiao Xiao; Ya-Li Zhang; Zi-An Zhou; Fan Wu; Hou-Feng Wang; Xin Zong (Science of The Total Environment, 2023)

Comprehensive evaluation of novel fungicide benzovindiflupyr at the enantiomeric level: Bioactivity, toxicity, mechanism, and dissipation behavior - Xiaokang An; Xinglu Pan; Runan Li; Fengshou Dong; Wentao Zhu; Jun Xu; Xiaohu Wu; Yongquan Zheng (Science of The Total Environment, 2023)

A hybrid framework for delineating the migration route of soil heavy metal pollution by heavy metal similarity calculation and machine learning method - Feng Wang; Lili Huo; Yue Li; Lina Wu; Yanqiu Zhang; Guoliang Shi; Yi An (Science of The Total Environment, 2023)

The local coupling and telecoupling of urbanization and ecological environment quality based on multisource remote sensing data - Wenjia Li; Min An; Hailin Wu; Hui An; Jin Huang; Ribesh Khanal (Journal of Environmental Management, 2023)

Portable colorimetric photonic indicator for ethanol concentration sensing - Yong Qi; Donghui Kou; Yudong Sun; Tong Hu; Hang Yuan; Changtong Zhou; Chang Li; An-Hui Lu; Suli Wu; Shufen Zhang (Chemical Engineering Journal, 2023)

Engineering manganese-rich phospho-olivine cathode materials with exposed crystal {0 1 0} facets for practical Li-ion batteries - Shaojun Liu; Jingang Zheng; Bo Zhang; Yingqiang Wu; Jinli Liu; Lianfang Yin; Miao Zhan; Yuanhua Xiao; Baigang An; Li Wang; Chengguo Sun; Xiangming He (Chemical Engineering Journal, 2023)

Inhibition of TGF-β pathway improved the pluripotency of porcine pluripotent stem cells - Fang Gao; Shuang Wu; Yan Li; Yuan Fang; Minli Liu; Jiawei Du; Qingran Kong; Tiezhu An (In Vitro Cellular & Developmental Biology - Animal, 2023)

Quantitative characterization and formation mechanism of the pore system heterogeneity: Examples from organic-rich laminated and organic-poor layered shales of the upper triassic chang 7 member in the southern Ordos Basin, China - Hao Lu; Qing Li; Dali Yue; Yue Wu; Jian Gao; Shenghe Wu; Wurong Wang; Mingqiang Li; Keqin An (Marine and Petroleum Geology, 2023)

Enhancing flotation removal of unburned carbon from fly ash by coal tar-based collector: Experiment and simulation - Kanghao Zheng; Wenjun Zhang; Yijiang Li; An Ping; Feng Wu; Guangyuan Xie; Wencheng Xia (Fuel, 2023)

A study on molecular structural evolution of type II kerogen in a gold tube thermal system: Insights from solid-state 13C NMR - Deping Zhang; Huairen Cao; Yan Lei; Hao Wu; Xiaoyu Wang; Xuelian Guo; Jianping Yan; Shuhua Wang; Tianchi Shi; Haolin Li; Yan-rong Zou; Ping'an Peng (Fuel, 2023)

Liquid metal embrittlement to boost reactivity and combustion performance of Al in composite propellants - An Chen; Bo Wu; Lan Li; Ting You; Jun Wang; Jinpeng Shen; Chonghua Pei (Fuel, 2023)

Synergistic effect of F doping and WO3 loading on electrocatalytic oxygen evolution - Ke Lu; Zongyuan Wang; Yaoxin Wu; Xingwu Zhai; Chenxu Wang; Ju Li; Zhimou Wang; Xinyi Li; Yuxuan He; Ting An; Kun Yang; Dezheng Yang; et al. (Chemical Engineering Journal, 2023)

Role of low-frequency wind variability in inducing WWBs during the onset of super El Niños - Yi-Kai Wu; Chi-Cherng Hong; Tim Li; An-Yi Huang (Climate Dynamics, 2023)

The prenatal weekly temperature exposure and neonatal congenital heart disease: a large population-based observational study in China - Weize Xu; Die Li; Zehua Shao; Yanqin You; Feixia Pan; Hongliang Lou; Jing Li; Yueqin Jin; Ting Wu; Lulu Pan; Jing An; Junqiu Xu; et al. (Environmental Science and Pollution Research, 2022)

Establishment of adventitious root culture system of Cynanchum wilfordii in air-lift bioreactors for the efficient production of bioactive compounds - Mei Wang; Miao Wang; Dong An; Chun-Hua Wu; Guang Li; Wei Wang; Xiao-Song Zhang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Plant, 2022)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Nucleosides and amino acids, isolated from Cordyceps sinensis, protected against cyclophosphamide-induced myelosuppression in mice - Yu Zhang; Jie Liu; Yan Wang; Chengpeng Sun; Wenjia Li; Jianjian Qiu; Yanling Qiao; Fan Wu; Xiaokui Huo; Yue An; Baojing Zhang; Shuangcheng Ma; et al. (Natural Product Research, 2022)

The landscape of aging - Yusheng Cai; Wei Song; Jiaming Li; Ying Jing; Chuqian Liang; Liyuan Zhang; Xia Zhang; Wenhui Zhang; Beibei Liu; Yongpan An; Jingyi Li; Baixue Tang; et al. (Science China Life Sciences, 2022)

Spinal Cord Mapping of Respiratory Intercostal Motoneurons in Adult Mice - Junhong Zhang; Fenlan Luo; Shuancheng Ren; Yaling Wang; Wu Li; Kan Xu; Ziyi Zheng; Chao He; Jianxia Xia; Wei Xiong; Zhi-An Hu (Neuroscience Bulletin, 2022)

Decoupling of water resources utilization and coordinated economic development in China’s Hexi Corridor based on ecological water resource footprint - Hailin Wu; Xiangyang Li; Hui An (Environmental Science and Pollution Research, 2022)

Maternal urine phthalate metabolite exposure and miscarriage risk: a nested case–control study of the Zunyi Birth Cohort - Xia Wang; Caidie He; Nian Wu; Yingkuan Tian; Linglu Wang; Juan Liao; Derong Fang; Xiang Liu; Songlin An; Wei Chen; Shimin Xiong; Yijun Liu; et al. (Environmental Science and Pollution Research, 2022)

Genome-wide identification of cysteine-rich receptor-like kinases in sweet cherry reveals that PaCRK1 enhances sweet cherry resistance to salt stress - Xiaohui Zhao; Dehui Qu; Lei Wang; Yuanhui Gao; Ningning An; Aiping Wang; Yaxin Li; Jingjing Yang; Fanlin Wu; Hongyan Su (Plant Cell Reports, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

Maternal exposure to cooking oil fumes during pregnancy and autistic‐like behaviors in Chinese preschoolers - Jian-Hui Yang; Esben Strodl; Chuan-An Wu; Xiang-Yu Hou; Xiao-Na Yin; Guo-Min Wen; Deng-Li Sun; Dan-Xia Xian; Jing-Yi Chen; Ying-Jie Chen; Jing Chen; Wei-Qing Chen (Environmental Science and Pollution Research, 2022)

A data-driven interpretable ensemble framework based on tree models for forecasting the occurrence of COVID-19 in the USA - Hu-Li Zheng; Shu-Yi An; Bao-Jun Qiao; Peng Guan; De-Sheng Huang; Wei Wu (Environmental Science and Pollution Research, 2022)

A fungal mycelium elicitor efficiently improved ginsenoside synthesis during adventitious root culture of Panax ginseng - X. L. An; Y. Yu; M. Z. Fan; X. H. Wu; X. F. Li; X. C. Piao; M. L. Lian (Journal of Plant Biochemistry and Biotechnology, 2022)

Elder people can be more susceptible to the association between short-term ambient air pollution and sleep disorder outpatient visits: a time-series study - Yu-Meng Zhou; Shu-Jie An; Yi Cao; Chen Xu; Xiao-Ling Liu; Chun-Yan Yao; Xiang Li; Na Wu; Cheng-Ying Li; Long Wu; Ya-Fei Li; Ai-Ling Ji; et al. (Environmental Science and Pollution Research, 2022)

Microfluidic preparation of a novel phoxim nanoemulsion pesticide against Spodoptera litura - Zong-Nan Li; Yu-Xuan Zhang; Zhi-Ang Zhang; Lian-Han Pan; Ping Li; Yan Xu; Sheng Sheng; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2022)

Exposure characteristics of phthalate metabolites among the Zunyi cohort of pregnant women in Southwest China - Juan Liao; Derong Fang; Yijun Liu; Shimin Xiong; Xia Wang; Yingkuan Tian; Haonan Zhang; Songlin An; Caidie He; Wei Chen; Xiang Liu; Nian Wu; et al. (Environmental Science and Pollution Research, 2022)

Study on the precipitation of iron and the synchronous removal mechanisms of antimony and arsenic in the AMD under the induction of carbonate rocks - Shihong Zhang; Ruixue Zhang; Pan Wu; Yahui Zhang; Yuran Fu; Li An; Yuhao Zhang (Environmental Science and Pollution Research, 2022)

Acute and chronic toxicities of prothioconazole and its metabolite prothioconazole-desthio in Daphnia magna - An Xuehua; Lui Xinju; Jiang Jinhua; Wang Feidi; Lv Lu; Li Gang; Wu Shenggan; Zhao Xueping (Environmental Science and Pollution Research, 2022)

Ambient temperature exposure and risk of outpatient visits for dermatologic diseases in Xinxiang, China: a time-series analysis - Ling Chao; Mengxue Lu; Wenshan Gao; Zhen An; Juan Li; Yue Liu; Weidong Wu; Jie Song (International Journal of Biometeorology, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Moderate intensity of static magnetic fields can alter the avoidance behavior and fat storage of Caenorhabditis elegans via serotonin - Lei Cheng; Baolin Yang; Hua Du; Tong Zhou; Yang Li; Jiajie Wu; Zhenxiao Cao; An Xu (Environmental Science and Pollution Research, 2022)

Analysis of the spatial distribution and influencing factors of China national forest villages - Guofang Gong; Zhen Wei; Fengtai Zhang; Yuzhen Li; Youzhi An; Qing Yang; Jianfeng Wu; Lu Wang; Pengzhen Yu (Environmental Monitoring and Assessment, 2022)

Geochemical characteristics and growth suitability assessment of Scutellaria baicalensis Georgi in the Earth’s critical zone of North China - Xia Li; Xiao-feng Wei; Jin Wu; Zhi-qiang Yin; Li-qin Wan; Hou-yun Sun; Yong-long An (Journal of Mountain Science, 2022)

Targeting GATA1 and p2x7r Locus Binding in Spinal Astrocytes Suppresses Chronic Visceral Pain by Promoting DNA Demethylation - Yan-Yan Wu; Hai-Long Zhang; Xiaomin Lu; Han Du; Yong-Chang Li; Ping-An Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2022)
Irritable bowel syndrome is a gastrointestinal disorder of unknown etiology characterized by widespread, chronic abdominal pain associated with altered bowel movements. Increasing amounts of evidence indicate that injury and inflammation during the neonatal period have long-term effects on tissue structure and function in the adult that may predispose to gastrointestinal diseases. In this study we aimed to investigate how the epigenetic regulation of DNA demethylation of the p2x7r locus guided by the transcription factor GATA binding protein 1 (GATA1) in spinal astrocytes affects chronic visceral pain in adult rats with neonatal colonic inflammation (NCI). The spinal GATA1 targeting to DNA demethylation of p2x7r locus in these rats was assessed by assessing GATA1 function with luciferase assay, chromatin immunoprecipitation, patch clamp, and interference in vitro and in vivo . In addition, a decoy oligodeoxynucleotide was designed and applied to determine the influence of GATA1 on the DNA methylation of a p2x7r CpG island. We showed that NCI caused the induction of GATA1, Ten-eleven translocation 3 (TET3), and purinergic receptors (P2X7Rs) in astrocytes of the spinal dorsal horn, and demonstrated that inhibiting these molecules markedly increased the pain threshold, inhibited the activation of astrocytes, and decreased the spinal sEPSC frequency. NCI also markedly demethylated the p2x7r locus in a manner dependent on the enhancement of both a GATA1–TET3 physical interaction and GATA1 binding at the p2x7r promoter. Importantly, we showed that demethylation of the p2x7r locus (and the attendant increase in P2X7R expression) was reversed upon knockdown of GATA1 or TET3 expression, and demonstrated that a decoy oligodeoxynucleotide that selectively blocked the GATA1 binding site increased the methylation of a CpG island in the p2x7r promoter. These results demonstrate that chronic visceral pain is mediated synergistically by GATA1 and TET3 via a DNA-demethylation mechanism that controls p2x7r transcription in spinal dorsal horn astrocytes, and provide a potential therapeutic strategy by targeting GATA1 and p2x7r locus binding.

Effects of ambient temperature on outpatient visits for dermatitis in Xinxiang, China: a time-series analysis - Ling Chao; Yajun Sun; Zhen An; Juan Li; Weidong Wu; Yue Liu; Jie Song (Environmental Science and Pollution Research, 2022)

Overexpression of ORX or MCH Protects Neurological Function Against Ischemic Stroke - Gang Wu; Xi’an Zhang; Shijun Li; Dan Zhou; Jie Bai; Hanxiang Wang; Qing Shu (Neurotoxicity Research, 2022)

Two new threonine-containing metabolites from fungus Curvularia inaequalis strain HS-FG-257 - Shao-Yong Zhang; Jian-Song Li; Hui Zhang; Huan Qi; Rui-Jun Wang; Chou-Fei Wu; Li-Qin Zhang; An-Liang Chen; Ji-Dong Wang; Zhi-Kui Hao (Natural Product Research, 2022)

Efficacy and safety of aripiprazole once-monthly versus oral aripiprazole in Chinese patients with acute schizophrenia: a multicenter, randomized, double-blind, non-inferiority study - Le Xiao; Qian Zhao; An-ning Li; Jushui Sun; Bin Wu; Lina Wang; Honggeng Zhang; Ruiling Zhang; Keqing Li; Xiaojin Xu; Tiebang Liu; Wenshun Zhang; et al. (Psychopharmacology, 2022)

Photosynthetic acclimation during low-light-induced leaf senescence in post-anthesis maize plants - Han-Yu Wu; Li-An Liu; Lei Shi; Wang-Feng Zhang; Chuang-Dao Jiang (Photosynthesis Research, 2021)

Effects of revegetation on the composition and diversity of bacterial and fungal communities of sandification land soil, in Southern China - Haozhi Long; Xiukun Wu; Yilin Wang; Junqing Yan; Xiaoyan Guo; Xuejiao An; Qinghua Zhang; Zhimin Li; Guanghua Huo (Environmental Monitoring and Assessment, 2021)

Effects of climate variables on the transmission of COVID-19: a systematic review of 62 ecological studies - Hu-Li Zheng; Ze-Li Guo; Mei-ling Wang; Chuan Yang; Shu-Yi An; Wei Wu (Environmental Science and Pollution Research, 2021)

Faster recovery of soil biodiversity in native species mixture than in Eucalyptus monoculture after 60 years afforestation in tropical degraded coastal terraces - Wenjia Wu; Luhui Kuang; Yue Li; Lingfeng He; Zhijian Mou; Faming Wang; Jing Zhang; Jun Wang; Zhi’an Li; Hans Lambers; Jordi Sardans; Josep Peñuelas; et al. (Global Change Biology, 2021)
Afforestation is an effective method to restore degraded land. Afforestation methods vary in their effects on ecosystem multifunctionality, but their effects on soil biodiversity have been largely overlooked. Here, we mapped the biodiversity and functioning of multiple soil organism groups resulting from diverse afforestation methods in tropical coastal terraces. Sixty years after afforestation from bare land (BL), plant species richness and the abundance of plant litter (398 ± 85 g m −2 ) and plant biomass (179 ± 3.7 t ha −1 ) in native tree species mixtures (MF) were restored to the level of native forests (NF; 287 ± 21 g m −2 and 243.0 ± 33 t ha −1 , respectively), while Eucalyptus monoculture (EP) only successfully restored the litter mass (388 ± 43 g m −2 ) to the level of NF. Soil fertility in EP and MF was increased but remained lower than in NF. For example, soil nitrogen and phosphorus concentrations in MF (1.2 ± 0.2 g kg −1 and 408 ± 49 mg kg −1 , respectively; p −1 and 523 ± 24 mg kg −1 , respectively; p

Short-term effect of NO2 on outpatient visits for dermatologic diseases in Xinxiang, China: a time-series study - Ling Chao; Mengxue Lu; Zhen An; Juan Li; Yuchun Li; Qian Zhao; Yinbiao Wang; Yue Liu; Weidong Wu; Jie Song (Environmental Geochemistry and Health, 2021)

Chronic Cyanuric Acid Exposure Depresses Hippocampal LTP but Does Not Disrupt Spatial Learning or Memory in the Morris Water Maze - Wei Sun; Yang Yang; Zexiang Wu; Xiao Chen; Wen Li; Lei An (Neurotoxicity Research, 2021)

Lignin Synthesis Related Genes with Potential Significance in the Response of Upland Cotton to Fusarium Wilt Identified by Transcriptome Profiling - Jianan Hou; Fu’an Zhao; Xiaojie Yang; Wu Li; Deyi Xie; Zhongjie Tang; Shuping Lv; Lihong Nie; Yao Sun; Mengmeng Wang; Yajing Zhu; Xiaopei Bo; et al. (Tropical Plant Biology, 2021)
Fusarium wilt, caused by the fungus Fusarium oxysporum Schlecht. f. sp. vasinfectum (Fov) is a destructive soil-borne cotton disease. To profile the genes and pathways responding to Fov infection, we compared transcriptomic responses before and after F. oxysporum inoculation in a highly resistant cotton cultivar, Yumian21, and a highly susceptible cultivar, Jimian11. Although the overall gene expression pattern was downregulated in both cultivars, the global gene expression in the resistant cultivar was stronger than that in the susceptible cultivar. In addition, the expressed genes of two cultivars mostly differed in “cellular process,” “single-organism process,” “metabolic process,” and “response to stimulus” functional groups in the biological process Gene Ontology category: the upregulated differentially expressed genes (DEG) were largely enriched in the resistant cultivar, while the downregulated DEGs were largely enriched in the susceptible cultivar. Phenylpropanoid biosynthesis and phenylalanine metabolism are the key metabolic pathways in cotton in response to Fov. We found that lignin plays a potential role in cotton resistance to Fov. Two coding genes, caffeic acid 3-O-methyltransferase and peroxidase2 , as well as the two transcription factors MYB46 and MYB86 , are possibly involved in the accumulation and synthesis of lignin. Furthermore, the result showed that the quantification of lignin could be potentially used as a selection tool to identify Fusarium wilt resistant cotton.

Enhancement of IUdR Radiosensitization in Cancer Therapy by Low-Energy Transmission X Ray Irradiation - Chien-Chih Ke; Jia-Je Li; Hsueh-Peng Wu; Wen-Wang Kuo; Yi-An Chen; Cheng-Hsiu Lu; Hsin-Ell Wang; Shih-Ming Hsu; Ya-Ju Hsieh; Ren-Shyan Liu (Journal of Medical and Biological Engineering, 2021)

Assessing the responses of hydrological drought to meteorological drought in the Huai River Basin, China - Jiayun Li; Chuanhao Wu; Chuan-An Xia; Pat J.-F. Yeh; Bill X. Hu; Guoru Huang (Theoretical and Applied Climatology, 2021)

Exogenous ABA and its inhibitor regulate flower bud induction of apple cv. ‘Nagafu No. 2′ grafted on different rootstocks - Wen-Fang Li; Juan Mao; Jing Su; Xin-Wen Li; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Trees, 2021)

Impacts of native vegetation on the hydraulic properties of the concentrated flows in bank gullies - Zheng-an Su; Zhou-yao He; Tao Zhou; Jun-jie Wang; Xiao-yi Wang; Li-juan Wang; Hai-dong Fang; Liang-tao Shi; Yi-han Liu; Zuo Wu (Journal of Mountain Science, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Temporal variation of airborne fungi in university library rooms and its relation to environmental parameters and potential confounders - Dingmeng Wu; Ying Zhang; Chenbo Zhao; Angui Li; Li’an Hou; Yu Tian; Jing Xiong; Ran Gao (Environmental Science and Pollution Research, 2021)

Evaluation and application of an efficient plant DNA extraction protocol for laboratory and field testing - Qi Wang; Xiaoxia Shen; Tian Qiu; Wei Wu; Lin Li; Zhi’an Wang; Huixia Shou (Journal of Zhejiang University-SCIENCE B, 2021)

Acute effects of ambient air pollution on outpatients with chronic rhinitis in Xinxiang, China - Mengxue Lu; Huijuan Yang; Jingyao Wang; Zhen An; Juan Li; Zhineng Wu; Qian Zhao; Huijun Li; Desheng Zhai; Yue Liu; Weidong Wu; Jie Song (Environmental Science and Pollution Research, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Phosphorus addition decreases microbial residual contribution to soil organic carbon pool in a tropical coastal forest - Ye Yuan; Yue Li; Zhijian Mou; Luhui Kuang; Wenjia Wu; Jing Zhang; Faming Wang; Dafeng Hui; Josep Peñuelas; Jordi Sardans; Hans Lambers; Jun Wang; et al. (Global Change Biology, 2021)
The soil nitrogen (N) and phosphorus (P) availability often constrains soil carbon (C) pool, and elevated N deposition could further intensify soil P limitation, which may affect soil C cycling in these N‐rich and P‐poor ecosystems. Soil microbial residues may not only affect soil organic carbon (SOC) pool but also impact SOC stability through soil aggregation. However, how soil nutrient availability and aggregate fractions affect microbial residues and the microbial residue contribution to SOC is still not well understood. We took advantage of a 10‐year field fertilization experiment to investigate the effects of nutrient additions, soil aggregate fractions, and their interactions on the concentrations of soil microbial residues and their contribution to SOC accumulation in a tropical coastal forest. We found that continuous P addition greatly decreased the concentrations of microbial residues and their contribution to SOC, whereas N addition had no significant effect. The P‐stimulated decreases in microbial residues and their contribution to SOC were presumably due to enhanced recycling of microbial residues via increased activity of residue‐decomposing enzymes. The interactive effects between soil aggregate fraction and nutrient addition were not significant, suggesting a weak role of physical protection by soil aggregates in mediating microbial responses to altered soil nutrient availability. Our data suggest that the mechanisms driving microbial residue responses to increased N and P availability might be different, and the P‐induced decrease in the contribution of microbial residues might be unfavorable for the stability of SOC in N‐rich and P‐poor tropical forests. Such information is critical for understanding the role of tropical forests in the global carbon cycle.

Magnesium decreases aluminum accumulation and plays a role in protecting maize from aluminum-induced oxidative stress - Xiangying Kong; Zhongping Peng; Dongxu Li; Wenna Ma; Ruidong An; Dawood Khan; Xinxun Wang; Yuan Liu; En Yang; Yuzhi He; Liqngquan Wu; Baige Zhang; et al. (Plant and Soil, 2020)

Identifying ephemeral gullies from high-resolution images and DEMs using flow-directional detection - Wen Dai; Guang-hui Hu; Xin Yang; Xian-wu Yang; Yi-han Cheng; Li-yang Xiong; Josef Strobl; Guo-an Tang (Journal of Mountain Science, 2020)

Effect of Bedding Plane on the Permeability Evolution of Typical Sedimentary Rocks Under Triaxial Compression - Yingchun Li; Chuangzhou Wu; Bo-An Jang (Rock Mechanics and Rock Engineering, 2020)

Acute effects of ambient air pollution on hospital outpatients with chronic pharyngitis in Xinxiang, China - Xiangmei Zhao; Mengxue Lu; Zhen An; Juan Li; Huijun Li; Qian Zhao; Zhineng Wu; Weidong Wu; Yue Liu; Jie Song (International Journal of Biometeorology, 2020)

A three-dimensional stratigraphic model of the Mississippi River Delta, USA: implications for river deltaic hydrogeology - An Li; Frank T.-C. Tsai; Brendan T. Yuill; Chenliang Wu (Hydrogeology Journal, 2020)

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Treatment Effect Analysis on Shallow Buried Bias Slope Section of Tunnel Based on Fuzzy Comprehensive Evaluation - Zhengjun Mao; Ning An; Ruting Li; Licheng Xu; Hao Wu (Geotechnical and Geological Engineering, 2020)

Proposal for Unification of the Genus Metakosakonia and the Genus Phytobacter to a Single Genus Phytobacter and Reclassification of Metakosakonia massiliensis as Phytobacter massiliensis comb. nov. - Yuanyuan Ma; Rong Yao; Yuanyuan Li; Xiuqin Wu; Shuying Li; Qianli An (Current Microbiology, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Overexpression of Purinergic P2X4 Receptors in Hippocampus Rescues Memory Impairment in Rats with Type 2 Diabetes - Ping-An Zhang; Qian Sun; Yong-Chang Li; Rui-Xia Weng; Rui Wu; Hong-Hong Zhang; Guang-Yin Xu (Neuroscience Bulletin, 2020)
Purinergic receptors have been reported to be involved in brain disorders. In this study, we explored their roles and mechanisms underlying the memory impairment in rats with type 2 diabetes mellitus (T2DM). T2DM rats exhibited a worse performance in the T-maze and Morris water maze (MWM) than controls. Microglia positive for P2X purinoceptor 4 (P2X4R) in the hippocampus were reduced and activated microglia were increased in T2DM rats. Long Amplicon PCR (LA-PCR) showed that DNA amplification of the p2x4r gene in the hippocampus was lower in T2DM rats. Minocycline significantly reduced the number of activated microglia and the mean distance traveled by T2DM rats in the MWM. Most importantly, P2X4R overexpression suppressed the activated microglia and rescued the memory impairment of T2DM rats. Overall, T2DM led to excessive activation of microglia in the hippocampus, partly through the DNA damage-mediated downregulation of P2X4Rs, thus contributing to memory impairment.

Recommended turbulent energy dissipation rate for biomass and lipid production of Scenedesmus obliquus in an aerated photosynthetic culture system - Mei An; Songqi Yang; Haiming Wu; Guanghong Luo; Ming Li (Environmental Science and Pollution Research, 2020)

Associations between air pollution and outpatient visits for allergic rhinitis in Xinxiang, China - Jingyao Wang; Mengxue Lu; Zhen An; Jing Jiang; Juan Li; Yinbiao Wang; Shuang Du; Xuexing Zhang; Haofeng Zhou; Juan Cui; Weidong Wu; Yue Liu; et al. (Environmental Science and Pollution Research, 2020)

Forecasting solar irradiation based on influencing factors determined by linear correlation and stepwise regression - Jun Qiu; Xiao-Jie An; Zhi-Gang Wu; Fang-Fang Li (Theoretical and Applied Climatology, 2020)

Cardiac-specific LRP6 knockout induces lipid accumulation through Drp1/CPT1b pathway in adult mice - Ying Wang; Chao Yin; Zhidan Chen; Yang Li; Yan Zou; Xiang Wang; Yanpeng An; Feizhen Wu; Guoping Zhang; Chunjie Yang; Huiru Tang; Yunzeng Zou; et al. (Cell and Tissue Research, 2020)

A New Shear Strength Criterion of Three-Dimensional Rock Joints - Yingchun Li; Chun’an Tang; Danqi Li; Chuangzhou Wu (Rock Mechanics and Rock Engineering, 2020)

Biallelic INTS1 Mutations Cause a Rare Neurodevelopmental Disorder in Two Chinese Siblings - Xuemin Zhang; Yajian Wang; Fang Yang; Jiulai Tang; Xiaoyan Xu; Li Yang; Xiu-An Yang; De Wu (Journal of Molecular Neuroscience, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Nogo-A/Pir-B/TrkB Signaling Pathway Activation Inhibits Neuronal Survival and Axonal Regeneration After Experimental Intracerebral Hemorrhage in Rats - Yinlong Liu; Chao Ma; Haiying Li; Haitao Shen; Xiang Li; Xi’an Fu; Jiang Wu; Gang Chen (Journal of Molecular Neuroscience, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Effects of CEPA and 1-MCP on Flower Bud Differentiation of Apple cv. ‘Nagafu No.2’ Grafted on Different Rootstocks - Wen-Fang Li; Juan Mao; Xin-Wen Li; Jing Su; Mohammed Mujitaba Dawuda; Zong-Huan Ma; Cun-Wu Zuo; Ze-Shan An; Bai-Hong Chen (Journal of Plant Growth Regulation, 2019)

Investigating the effect of methyl jasmonate and melatonin on resistance of Malus crabapple ‘Hong Jiu’ to ozone stress - Yanfen Qiu; Kai An; Jingjing Sun; Xuesen Chen; Xiaojun Gong; Li Ma; Shuqing Wu; Shenghui Jiang; Zongying Zhang; Yanling Wang (Environmental Science and Pollution Research, 2019)

A facile hydrothermal method–fabricated robust and ultralight weight cellulose nanocrystal-based hydro/aerogels for metal ion removal - Xuehua Liu; Mingcong Xu; Bang An; Zhenwei Wu; Rue Yang; Chunhui Ma; Qiongtao Huang; Wei Li; Jian Li; Shouxin Liu (Environmental Science and Pollution Research, 2019)

A review on the research status and development trend of equipment in water treatment processes of recirculating aquaculture systems - Ruichao Xiao; Yaoguang Wei; Dong An; Daoliang Li; Xuxiang Ta; Yinghao Wu; Qin Ren (Reviews in Aquaculture, 2019)
Recirculating aquaculture systems ( RAS s) are intensive aquaculture facilities models that depend on diverse water treatment equipment to maintain good water quality and produce safe and healthy high‐quality aquatic products. This article combines the main farming‐mode of water purification recirculating processes with recent cultivation‐mode scientific research and the current development of the recirculating aquaculture industry. Harmful substances are present in aquaculture wastewater due to large quantities of residual particulate matter such as residual feed, faeces and small suspended solid particles, as well as ammonia, nitrite, bacteria and carbon dioxide ( CO 2 ), in the water. These harmful substances seriously affect the quality of aquatic products, so water treatment equipment is needed to remove these substances, add oxygen (O 2 ) to the water and adjust the temperature of the water to ensure a high‐quality environment for fish survival. This article reviews the equipment for physical filtration (e.g. solid–liquid separation equipment, microscreen drum filter and foam fractionator) that could remove suspended solids during the water treatment of RAS s and the equipment for biological filtration (e.g. fluidized sand biofilter ( FSB ), moving‐bed biofilm reactor ( MBBR ) and rotating biological contactor ( RBC )) that could remove ammonia nitrogen, nitrite and other hazardous substances from wastewater, as well as equipment for water disinfection and sterilization, O 2 addition, CO 2 removal and temperature control. Comprehensive analysis and discussion of water treatment efficiency are provided for reference to create efficient high‐end recirculation aquaculture models and increase the precision and intelligence degree of recirculating water treatment technologies in the future.

Genome-wide analysis of maize GPAT gene family and cytological characterization and breeding application of ZmMs33/ZmGPAT6 gene - Taotao Zhu; Suowei Wu; Danfeng Zhang; Ziwen Li; Ke Xie; Xueli An; Biao Ma; Quancan Hou; Zhenying Dong; Youhui Tian; Jinping Li; Xiangyuan Wan (Theoretical and Applied Genetics, 2019)

SNP development and diversity analysis for Ginkgo biloba based on transcriptome sequencing - Yaqiong Wu; Qi Zhou; Shujing Huang; Guibin Wang; Li-an Xu (Trees, 2019)

Environmentally friendly methodology for fouling removal in pipeline based on leaky guided wave generated by quasi-axisymmetric excitation mode - Shuqing Li; Ri Fang; Zhigang Qu; Liqun Wu; Yang An; Ying Liu; Jie Yang; Shuo Jin; Wuliang Yin (Clean Technologies and Environmental Policy, 2019)

The optimized condition for the isolation and in vitro propagation of mouse spermatogonial stem cells - Fahar Ibtisham; Yi Zhao; Jiang Wu; Aamir Nawab; Xiao Mei; GuangHui Li; Lilong An (Biologia Futura, 2019)

Undrained shear strength evaluation for hydrate-bearing sediment overlying strata in the Shenhu area, northern South China Sea - Yanlong Li; Gaowei Hu; Nengyou Wu; Changling Liu; Qiang Chen; Chen’an Li (Acta Oceanologica Sinica, 2019)

N-(3-oxo-acyl) homoserine lactone induced germ cell apoptosis and suppressed the over-activated RAS/MAPK tumorigenesis via mitochondrial-dependent ROS in C. elegans - Bin Chen; Xianbin Cao; Huayi Lu; Pengbo Wen; Xiaojing Qi; Shaopeng Chen; Lijun Wu; Chi Li; An Xu; Guoping Zhao (Apoptosis, 2018)

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)

Endophytic bacterium Buttiauxella sp. SaSR13 improves plant growth and cadmium accumulation of hyperaccumulator Sedum alfredii - Keren Wu; Jipeng Luo; Jinxing Li; Qianli An; Xiaoe Yang; Yongchao Liang; Tingqiang Li (Environmental Science and Pollution Research, 2018)

Description of a new species of Triplophysa (Teleostei: Nemacheilidae) from Guizhou Province, China - Wei‐Jun Wu; An‐You He; Jun‐Xing Yang; Li‐Na Du (Journal of Fish Biology, 2018)
A new cave‐dwelling fish species Triplophysa guizhouensis is described based on specimens collected from Guizhou, China, in a subterranean system interconnected with the Hongshui River drainage. The species can be distinguished from its congeners by a combination of characters: eyes present; caudal fin with 14 branched rays; inner gill rakers of first gill arch 8–10; posterior chamber of air bladder developed; and body posterior of dorsal fin scaled. A key to species of Triplophysa in the Pearl River basin is provided.

Map-based cloning and characterization of Zea mays male sterility33 (ZmMs33) gene, encoding a glycerol-3-phosphate acyltransferase - Ke Xie; Suowei Wu; Ziwen Li; Yan Zhou; Danfeng Zhang; Zhenying Dong; Xueli An; Taotao Zhu; Simiao Zhang; Shuangshuang Liu; Jinping Li; Xiangyuan Wan (Theoretical and Applied Genetics, 2018)

Red mud-modified biochar reduces soil arsenic availability and changes bacterial composition - Qi Zou; Wenhui An; Chuan Wu; Waichin Li; Anqin Fu; Ruiyang Xiao; Huikang Chen; Shengguo Xue (Environmental Chemistry Letters, 2018)

Enhancement of brain-targeting delivery of danshensu in rat through conjugation with pyrazine moiety to form danshensu-pyrazine ester - Ailing Hui; Huayang Yin; Zheng Zhang; An Zhou; Jingchao Chen; Li Yang; Zeyu Wu; Wencheng Zhang (Drug Delivery and Translational Research, 2018)

Both widespread PEP‐CTERM proteins and exopolysaccharides are required for floc formation of Zoogloea resiniphila and other activated sludge bacteria - Na Gao; Ming Xia; Jingcheng Dai; Dianzhen Yu; Weixing An; Shuyang Li; Shuangyuan Liu; Penghui He; Liping Zhang; Zhenbin Wu; Xuezhi Bi; Shouwen Chen; et al. (Environmental Microbiology, 2018)
Summary Bacterial floc formation plays a central role in the activated sludge (AS) process, which has been widely utilized for sewage and wastewater treatment. The formation of AS flocs has long been known to require exopolysaccharide biosynthesis. This study demonstrates an additional requirement for a PEP‐CTERM protein in Zoogloea resiniphila , a dominant AS bacterium harboring a large exopolysaccharide biosynthesis gene cluster. Two members of a wide‐spread family of high copy number‐per‐genome PEP‐CTERM genes, transcriptionally regulated by the RpoN sigma factor and accessory PrsK‐PrsR two‐component system and at least one of these, pepA , must be expressed for Zoogloea to build the floc structures that allow gravitational sludge settling and recycling. Without PrsK or PrsR, Zoogloea cells were planktonic rather than flocculated and secreted exopolysaccharides were released into the growth broth in soluble form. Overexpression of PepA could circumvent the requirement of rpoN , prsK and prsR for the floc‐forming phenotype by fixing the exopolysaccharides to bacterial cells. However, overexpression of PepA, which underwent post‐translational modifications, could not rescue the long‐rod morphology of the rpoN mutant. Consistently, PEP‐CTERM genes and exopolysaccharide biosynthesis gene cluster are present in the genome of the floc‐forming Nitrospira comammox and Mitsuaria strain as well as many other AS bacteria.

A terrain openness index for the extraction of karst Fenglin and Fengcong landform units from DEMs - Xin Meng; Li-yang Xiong; Xian-wu Yang; Bi-sheng Yang; Guo-an Tang (Journal of Mountain Science, 2018)

Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean - Tian-Yu Zhang; Jian-Jun Fan; Cai Li; Chao-Ming Xie; Ming Wang; Yan-Wang Wu; Meng-Jing Xu; Wei Xu; Jin-Heng Liu; An-Bo Luo (International Geology Review, 2018)

Release and kinetics of arsenic and plumbum in the Songhua River surficial sediments - Guang-Min Liu; Qing An; Li-Juan Wang; Xin Jia; Si-Hui Feng; Shu-Mei Xia; Yi-Ning Wu; Hong Qi (Environmental Science and Pollution Research, 2018)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

Genetic parameters for growth traits and stem-straightness in Eucalyptus urophylla × E. camaldulensis hybrids from a reciprocal mating design - Ying’an Zhu; ShiJun Wu; Jianmin Xu; Zhaohua Lu; Guangyou Li; Yang Hu; Xueyan Yang; David Bush (Euphytica, 2017)

Automatic recognition of loess landforms using Random Forest method - Wu-fan Zhao; Li-yang Xiong; Hu Ding; Guo-an Tang (Journal of Mountain Science, 2017)

A comprehensively quantitative method of evaluating the impact of drought on crop yield using daily multi-scale SPEI and crop growth process model - Qianfeng Wang; Jianjun Wu; Xiaohan Li; Hongkui Zhou; Jianhua Yang; Guangpo Geng; Xueli An; Leizhen Liu; Zhenghong Tang (International Journal of Biometeorology, 2017)

Spatio-temporal assessments of rockburst hazard combining b values and seismic tomography - Jing Li; Si-Yuan Gong; Jiang He; Wu Cai; Guang-An Zhu; Chang-Bin Wang; Tian Chen (Acta Geophysica, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Identification, isolation and expression analysis of eight stress-related R2R3-MYB genes in tartary buckwheat (Fagopyrum tataricum) - Fei Gao; Hai-Xia Zhao; Hui-Peng Yao; Cheng-Lei Li; Hui Chen; An-Hu Wang; Sang-Un Park; Qi Wu (Plant Cell Reports, 2016)

Characterization of the prokaryotic diversity through a stratigraphic permafrost core profile from the Qinghai-Tibet Plateau - Weigang Hu; Qi Zhang; Tian Tian; Dingyao Li; Gang Cheng; Jing Mu; Qingbai Wu; Fujun Niu; Lizhe An; Huyuan Feng (Extremophiles, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

Isolation, identification and genomic characterization of the Asian lineage Zika virus imported to China - Yong-Qiang Deng; Hui Zhao; Xiao-Feng Li; Na-Na Zhang; Zhong-Yu Liu; Tao Jiang; Da-Yong Gu; Lei Shi; Jian-An He; Hong-Jiang Wang; Zhao-Zeng Sun; Qing Ye; et al. (Science China Life Sciences, 2016)

Analysis the role of arabidopsis CKRC6/ASA1 in auxin and cytokinin biosynthesis - Dong-Wei Di; Lei Wu; Pan Luo; Li Zhang; Tian-Zi Zhang; Xue Sun; Shao-Dong Wei; Chen-Wei An; Guang-Qin Guo (Journal of Plant Biology, 2016)

Critical Length of Contaminant Cloud in a Three-Layer Wetland: Multi-scale Analysis for Environmental Dispersivity - Li Zhi; Wang Ping; Sun Tao; An Yiran; Wu Xudong (Wetlands, 2016)

Novel DOCK8 gene mutations lead to absence of protein expression in patients with hyper-IgE syndrome - Tao Qin; Yunfei An; Chaohong Liu; Junfeng Wu; Rongxin Dai; Dawei Liu; Xiaohui Li; Liping Jiang; Daoqi Wu; Xuemei Tang; Wenxia Song; Tao Wang; et al. (Immunologic Research, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Tadehaginoside modulates lipogenesis and glucose consumption in HepG2 cells - Xiaopo Zhang; Shuai Wang; Yonghui Li; Dan Zhao; Ni An; Jiani Wu; Tingting Zhang; Chongming Wu; Youbin Li (Natural Product Research, 2015)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

A new lignan with hypoglycemic activity from Tadehagi triquetrum - Jiani Wu; Cai yun Zhang; Tingting Zhang; Dan Zhao; Ni An; Youbin Li; Nailiang Zhu; Shuai Wang; Feng Chen; Xiaopo Zhang (Natural Product Research, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

A single-repeat MYB transcription repressor, MYBH, participates in regulation of leaf senescence in Arabidopsis - Chun-Kai Huang; Pei-Ching Lo; Li-Fen Huang; Shaw-Jye Wu; Ching-Hui Yeh; Chung-An Lu (Plant Molecular Biology, 2015)

Effect of auxin, cytokinin and nitrogen on anthocyanin biosynthesis in callus cultures of red-fleshed apple (Malus sieversii f.niedzwetzkyana) - Xiao-Hao Ji; Yan-Ting Wang; Rui Zhang; Shu-Jing Wu; Meng-Meng An; Min Li; Chuan-Zeng Wang; Xiao-Liu Chen; Yan-Min Zhang; Xue-Sen Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Nicotine-induced upregulation of VCAM-1, MMP-2, and MMP-9 through the α7-nAChR-JNK pathway in RAW264.7 and MOVAS cells - Zong-Zhuang Li; Zhen-Zhen Guo; Zhi Zhang; Qun-An Cao; Ya-Juan Zhu; Hua-Li Yao; Li-Li Wu; Qiu-Yan Dai (Molecular and Cellular Biochemistry, 2015)

Dynamic changes of serum cholinesterase activity after severe trauma - Li Ba; Ding-qian Wu; An-yu Qian; Mao Zhang; Bing Xiong (Journal of Zhejiang University-SCIENCE B, 2014)

Spatial distribution characteristics of surface tidal currents in the southwest of Taiwan Strait - Zhiben Shen; Xiongbin Wu; Hang Lin; Xiaofeng Chen; Xing’an Xu; Lun Li (Journal of Ocean University of China, 2014)

Posterior Trochanteric Osteotomy in Acetabular Fractures for 32 Cases - Yunfei Niu; Xiaofei An; Shuogui Xu; Dajiang Wu; Chuncai Zhang; Ming Li (Cell Biochemistry and Biophysics, 2014)

Isolation and characterization of LEAFY COTYLEDON 1-LIKE gene related to embryogenic competence in Citrus sinensis - Shi-ping Zhu; Jun Wang; Jun-li Ye; An-Dan Zhu; Wen-wu Guo; Xiu-xin Deng (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Divergence of the expression and subcellular localization of CCR4-associated factor 1 (CAF1) deadenylase proteins in Oryza sativa - Wei-Lun Chou; Li-Fen Huang; Jhen-Cheng Fang; Ching-Hui Yeh; Chwan-Yang Hong; Shaw-Jye Wu; Chung-An Lu (Plant Molecular Biology, 2014)

Oxidative Stress and Autophagic Alteration in Brainstem of SOD1-G93A Mouse Model of ALS - Ting An; Pengxiao Shi; Weisong Duan; Shipan Zhang; Pin Yuan; Zhongyao Li; Dongxia Wu; Zuoshang Xu; Chunyan Li; Yansu Guo (Molecular Neurobiology, 2014)

Efficacy and Safety of Parecoxib/Phloroglucinol Combination Therapy Versus Parecoxib Monotherapy for Acute Renal Colic: A Randomized, Double-Blind Clinical Trial - Weihua Fu; Jiwei Yao; Qianwei Li; Yongquan Wang; Xiaojun Wu; Zhansong Zhou; Wei-Bing Li; Jun-An Yan (Cell Biochemistry and Biophysics, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Integrated response of intercropped maize and potatoes to heterogeneous nutrients and crop neighbours - Bozhi Wu; M. A. Fullen; Jianbin Li; Tongxin An; Zhiwei Fan; Feng Zhou; Suhui Zi; Youqiong Yang; Guofeng Xue; Zhong Liu; Kaixian Wu (Plant and Soil, 2014)

Interleukin-18 promoter polymorphisms and plasma levels are associated with increased risk of periodontitis: a meta-analysis - Zhi-Gang Li; Jin-Juan Li; Chang-An Sun; Yuan Jin; Wei-Wei Wu (Inflammation Research, 2014)

Temporal Modulation of Sodium Current Kinetics in Neuron Cells by Near-Infrared Laser - Xinyu Li; Jia Liu; Shanshan Liang; Kuiwen Guan; Lijia An; Xuefei Wu; Shao Li; Changsen Sun (Cell Biochemistry and Biophysics, 2013)

Impacts of Urbanization and Station-relocation on Surface Air Temperature Series in Anhui Province, China - Yuan-Jian Yang; Bi-Wen Wu; Chun-e Shi; Jia-Hua Zhang; Yu-Bin Li; Wei-An Tang; Hua-Yang Wen; Hong-Qun Zhang; Tao Shi (Pure and Applied Geophysics, 2013)

Immortalized mouse dental papilla mesenchymal cells preserve odontoblastic phenotype and respond to bone morphogenetic protein 2 - Feng Wang; Li-An Wu; Wentong Li; Yuan Yang; Feng Guo; Qingping Gao; Hui-Hsiu Chuang; Lisa Shoff; Wei Wang; Shuo Chen (In Vitro Cellular & Developmental Biology - Animal, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Increased precipitation during the Little Ice Age in northern Taiwan inferred from diatoms and geochemistry in a sediment core from a subalpine lake - Liang-Chi Wang; Hermann Behling; Teh-Quei Lee; Hong-Chun Li; Chih-An Huh; Liang-Jian Shiau; Su-Hwa Chen; Jiunn-Tzong Wu (Journal of Paleolimnology, 2013)

Spatiotemporal Variations in Nitrous Oxide Emissions from an Open Fen on the Qinghai–Tibetan Plateau: a 3-Year Study - Huai Chen; Yanfen Wang; Ning Wu; Dan Zhu; Wei Li; Yongheng Gao; Qiu’an Zhu; Gang Yang; Changhui Peng (Water, Air, & Soil Pollution, 2012)

Susceptibilities to Amphotericin B, Fluconazole and Voriconazole of Trichosporon Clinical Isolates - Moan Shane Tsai; Yun Liang Yang; An Huei Wang; Lih Shinn Wang; Daniel C. T. Lu; Ci Hong Liou; Li Yun Hsieh; Chi Jung Wu; Ming Fang Cheng; Zhi Yuan Shi; Hsiu Jung Lo (Mycopathologia, 2012)

Glutathione peroxidase from the white shrimp Litopenaeus vannamei: characterization and its regulation upon pH and Cd exposure - Lei Wang; Juan Wu; Wei-Na Wang; Dan-Xia Cai; Yuan Liu; An-Li Wang (Ecotoxicology, 2012)

The respiratory burst activity and expression of catalase in white shrimp, Litopenaeus vannamei, during long-term exposure to pH stress - Wei-Na Wang; Bao-Sheng Li; Jin-Jian Liu; Lei Shi; M. J. Alam; Shi-Juan Su; Juan Wu; Lei Wang; An-Li Wang (Ecotoxicology, 2012)

Response to weaning and dietary l-glutamine supplementation: metabolomic analysis in piglets by gas chromatography/mass spectrometry - Ying-ping Xiao; Tian-xing Wu; Qi-hua Hong; Jiang-ming Sun; An-guo Chen; Cai-mei Yang; Xiao-yan Li (Journal of Zhejiang University-SCIENCE B, 2012)

The conditioned medium from a stable human GDF3-expressing CHO cell line, induces the differentiation of PC12 cells - Qiang Li; Xianghua Liu; Yanhua Wu; Jian An; Saiyin Hexige; Yichen Ling; Mingjun Zhang; Xianmei Yang; Long Yu (Molecular and Cellular Biochemistry, 2012)

Effect of glucocorticoids pretreatment on steroidogenic capacity of adrenocortical cells isolated from Meishan piglets - Liu-An Li; Zhan-Wang Wu; Xiao-Jing Yang; Ying-Dong Ni; Nahid Parvizi; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Development and characterization of a mouse floxed Bmp2 osteoblast cell line that retains osteoblast genotype and phenotype - Li-an Wu; Junsheng Feng; Lynn Wang; Yan-dong Mu; Andrew Baker; Kevin J. Donly; Stephen E. Harris; Mary MacDougall; Shuo Chen (Cell and Tissue Research, 2011)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)

Detection of Leptosphaeria maculans from imported Canola seeds - G. Y. Chen; C. P. Wu; B. Li; H. Su; S. Z. Zhen; Y. L. An (Journal of Plant Diseases and Protection, 2010)

An automatic scheme for baseline correction of strong-motion records in coseismic deformation determination - Wei-An Chao; Yih-Min Wu; Li Zhao (Journal of Seismology, 2010)

Molecular Characterisation of the Faecal Microbiota in Patients with Type II Diabetes - Xiaokang Wu; Chaofeng Ma; Lei Han; Muhammad Nawaz; Fei Gao; Xuyan Zhang; Pengbo Yu; Chang’an Zhao; Lianchuan Li; Aiping Zhou; Juan Wang; John E. Moore; et al. (Current Microbiology, 2010)

Assessment of dissolved heavy metal in the Yangtze River estuary and its adjacent sea, China - Qiang An; Yanqing Wu; Jinhui Wang; Zhien Li (Environmental Monitoring and Assessment, 2010)

Evaluation of genetic diversity in Lentinula edodes strains using RAPD, ISSR and SRAP markers - Li-Zhong Fu; Hong-Yu Zhang; Xue-Qian Wu; Hai-Bo Li; Hai-Long Wei; Qing-Qi Wu; Li-An Wang (World Journal of Microbiology and Biotechnology, 2010)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Autotoxicity of wheat (Triticum aestivum L.) as determined by laboratory bioassays - Hanwen Wu; Jim Pratley; Deirdre Lemerle; Min An; De Li Liu (Plant and Soil, 2007)

Land cover changes in the rural-urban interaction of Xi’an region using Landsat TM/ETM data - Jiang Jianjun; Zhou Jie; Wu Hong’an; Ai Li; Zhang Hailong; Zhang Li; Xu Jun (Journal of Geographical Sciences, 2005)

Inhibition of neuropathy target esterase expressing by antisense RNA does not affect neural differentiation in human neuroblastoma (SK-N-SH) cell line - Ping-An Chang; Yi-Jun Wu; Rui Chen; Ming Li; Wei Li; Qi-Lian Qin (Molecular and Cellular Biochemistry, 2005)

Bacterial diversity in malan ice core from the Tibetan Plateau - S. R. Xiang; T. D. Yao; L. Z. An; B. Q. Xu; Z. Li; G. J. Wu; Y. Q. Wang; S. Ma; X. R. Chen (Folia Microbiologica, 2004)

Enhancing ethanol tolerance of a self-flocculating fusant of Schizosaccharomyces pombe and Saccharomyces cerevisiae by Mg2+ via reduction in plasma membrane permeability - Chun-Keng Hu; Feng-Wu Bai; Li-Jia An (Biotechnology Letters, 2003)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Interannual and decadal variability of landfalling tropical cyclones in the southeast coastal states of the united states - Li'an Xie; Leonard J. Pietrafesa; Kejian Wu (Advances in Atmospheric Sciences, 2002)

Beneficial effect of HCL-31D in murine models of endotoxaemia - Tz-Chong Chou; Chi-Yuan Li; Tzong-Ming Wu; Shang-Tao Tang; An-Rong Lee; Yu-An Ding (Naunyn-Schmiedeberg's Archives of Pharmacology, 2001)